Lactic acid bacteria bacteriocins as novel antimicrobials against antibiotic-resistant Streptococcus pneumoniae in opthalamic infections - Marriam Wasif; Nazish Mazhar Ali; Syed Abdullah Mazhar; Sher Muhammad Zaman; Seher kiran; Maham Chaudhry; Ibtissem Louiz; Amor Hedfi; Manel Ben Ali; Arslan Muhammad Ali Khan; Itrat Zahra (Molecular Biology Reports, 2026)

Molecular characterization and vaccine matching of foot-and-mouth disease virus in Khyber Pakhtunkhwa, Pakistan - Muhammad Sajid; Muhammad Ali Syed; Abdul Kabir; Asghar Ali Kamboh; Muhammad Mumtaz Khan (Molecular Biology Reports, 2026)

Exogenous dopamine alleviates chilling injury of sapodilla (Manilkara zapota) fruit by modulating reactive oxygen species and ascorbate-glutathione cycle activities - Sajid Ali; Syed Muhammad Kashan Haider; Safina Naz; Hafiz Umer Javed; Aamir Nawaz; Shaghef Ejaz; Muhammad Shahzad Saleem (Postharvest Biology and Technology, 2026)

Partitioning of granular flows at valley bifurcation under varying control conditions - Hasnain Gardezi; Xingyue Li; Yu Huang; Syed Muhammad Mudassir Zia; Irtza Ali; Taimur Mazhar Sheikh (Engineering Geology, 2026)

Engineering of novel N-TiO2/P-doped graphene oxide nanocomposite: Mechanistic insights into the photocatalytic removal of benzophenone-3 and H2 production - Wisal Ahmad; Suyeon Jeon; Roman Shah; Dilaram Khan; Syed Izaz Ali Shah; Muhammad Anwar; Raed Al-Juboori; Asad Ali; Noor S. Shah; Javed Ali Khan; Changseok Han (Chemical Engineering Journal, 2026)

Fenugreek seed extract supplementation: a mitigating strategy against tannery effluent toxicity in Catla catla - Muhammad Amjad; Syed Makhdoom Hussain; Salma Sultana; Shafaqat Ali; Hesham A. Hassanien (Veterinary Research Communications, 2026)

Reversible -NH2/-NH3+ switching drives proton-coupled electron transfer for selective CO2-to-CO photoreduction in S-scheme MOF/g-C3N4 heterojunction - Sharafat Ali; Sher Ali; Ahmed Ismail; Yong Wang; Syed Ul Hasnain Bakhtiar; Qaisar Alam; Pir Muhammad Ismail; Wajid Ali; Ahmad Iqbal; Polycarpos Falaras; Jiabao Yi; Fazal Raziq; et al. (Chemical Engineering Journal, 2026)

A review on sustainable aviation fuel production via diverse biomass and waste-derived feedstocks and cutting-edge conversion technologies - Wajahat Waheed Kazmi; Muhammad Wasi Syed; Muhammad Waqas; Umair Hassan Bhatti; Ahmed Omer; Mansoor Ali; Zulqarnain; Ishaq Kariim; Amjad Hussain; Faysal M. Al-Khulaifi (Biomass and Bioenergy, 2026)

Retraction Note: Ameliorating Nickel-Induced Stress in Hypophthalmichthys molitrix (Silver Carp) Through Piper nigrum Extract Supplementation - Syed Muhammad Farhan Ali Shah; Syed Makhdoom Hussain; Shafaqat Ali; Pallab K Sarker; Khalid A. Al-Ghanim; Sunakbaeva Dilara (Biological Trace Element Research, 2026)

Retraction notice to “Environmentally responsive and anti-bugs textile finishes – Recent trends, challenges, and future perspectives” [Sci. Total Environ. 690 (2019) 667–682] - Shahzad Ali Shahid Chatha; Muhammad Asgher; Rabbia Asgher; Abdullah Ijaz Hussain; Yasir Iqbal; Syed Makhdoom Hussain; Muhammad Bilal; Faizan Saleem; Hafiz M.N. Iqbal (Science of The Total Environment, 2026)

Diesel engine performance enhancement using MXene nano-additives: An experimental study on efficiency and Pollutant Suppression - Mohd Danish; Sajid Ali; Syed Mohd Yahya; Rashid Ali; Suhaib Umer Ilyas; Sami Mansour Ghazali; Muhammad Faisal Rathore; Saeed Rubaiee (Fuel, 2026)

The role of Campylobacter group II phages in mitigating Campylobacter contamination across the poultry food chain: Current applications and future prospects - Muhammad Shahzad Rafiq; Syed Sami Haider; Ziyi Li; Muhammad Sarmad; Dongxin Ma; Muhammad Ali Khan; Junhao Wang; Shuaifeng Gu; Pan Tao; Muhammad Tanweer Khan; Haihong Hao (Food Research International, 2026)

Morphology and phylogeny reveal a New Species and Two New Combinations of Xerocomellus (Boletaceae) from Bajaur, Pakistan - Mohsin Ullah; Malka Saba; Syed Mohammad Tauseeq Ali Shah; Dege Zheng; Umer Rehman; Atika Noor; Muhammad Asif; Dong-Qin Dai; Ishtiaq Ahmad; Samantha C. Karunarathna (Current Microbiology, 2026)

Biomedical applications of fungal-derived nanoparticles: bridging mycology and nanotechnology for next-generation therapeutics - Umer Rehman; Mohsin Ullah; Syed Mohammad Tauseeq Ali Shah; Muhammad Adnan; Ishtiaq Ahmad; Zabta Khan Shinwari (Plant Biosystems, 2026)

Molecular mechanisms underlaying fluoride-induced neurotoxicity: interplay of antioxidants and endoplasmic reticulum stress–mediated apoptotic pathways in rats - Ashiru Dahiru; Ismat Nawaz; Syeda Kiran Riaz; Summaya Sohail Chaudry; Muhammad Jadoon Khan; Qingyu Huang; Muhammad Abbas; Syed Ali Musstjab Akber Shah Eqani (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Pharmacokinetic evaluation and in vivo anti-inflammatory potential of cyanoacetate derivatives of succinimide - Aini Pervaiz; Muhammad Saeed Jan; Ali Khan; Bushra Ansari; Imad Ahmad; Wadood Ali Shah; Syed Muhammad Mukarram Shah; Abdur Rauf; Abdullah S. M. Aljohani; Waleed Al Abdulmonem; Marcello Iriti (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
The purpose of the study is to evalute the in vivo anti -inflammatory activity of newly synthesized cyanoacetate derivatives of succinimides (C-23, C-31, and C-44) and to elucidate their possible mechanisms of action through key inflammatory mediator pathways. Anti-inflammatory activity was assessed using carrageenan-induced paw oedema and arachidonic acid-induced ear oedema models in vivo. Mechanistic involvement was investigated through histamine-, prostaglandin-, leukotriene-, and bradykinin-induced paw oedema assays. In silico ADME studies were performed to predict pharmacokinetic properties and metabolic interactions. All tested compounds exhibited significant anti-inflammatory activity, with C-44 showing the highest potency. Mechanistic studies indicated that the anti-inflammatory effects were predominantly mediated via inhibition of prostaglandin and leukotriene pathways. ADME predictions suggested high gastrointestinal absorption, favourable oral bioavailability, and minimal interaction with major metabolic enzymes. The synthesized cyanoacetate derivatives, particularly C-44, demonstrate promising anti-inflammatory potential with favourable pharmacokinetic profiles, supporting their candidacy for further development as effective anti-inflammatory agents.

Unraveling Luteolin’s Modulatory Effects on α-Synuclein Aggregation: A Combined Biophysical, Computational, and C. elegans Approach - Syed Moasfar Ali; Md Nadir Hassan; Nida Zaidi; Muhammad Uzair Ashraf; Mahmood Akbar; Aamir Nazir; Rizwan Hasan Khan (Cell Biochemistry and Biophysics, 2026)

Integrative reverse vaccinology and computational modeling for the rational design of a broadly immunogenic multi-epitope vaccine against Marburg virus infection - Asadullah Khan; Sitara Bibi; Li Pinyi; Khalida Latif; Muhammad Rahiyab; Ishaq Khan; Arshad Iqbal; Itazaz Ul Haq; Syed Shujait Ali (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Lactobacilli Mitigate Gut Inflammation by Modulating T-Helper/T-Regulatory Cells and Suppressing Signaling Pathways in Food-Derived Models - Md. F. Kulyar; Syed Umair Ali Shah Naqvi; Eiva Bernotiene; Muhammad Akhtar (Probiotics and Antimicrobial Proteins, 2026)
Intestinal inflammation disrupts epithelial integrity, fuels antibiotic resistance, and underlies disorders such as inflammatory bowel disease. Lactobacillus species, established inhabitants of traditional and contemporary fermented foods, are increasingly viewed as bioactive cultures that shape host immunity and support formulation of next-generation functional foods. This review integrates multidisciplinary evidence from in vitro studies, animal models, human observations, and multi omics datasets to clarify how dietary or probiotic Lactobacillus strains alleviate gut inflammation. Particular attention is given to strain specific effects on T-helper/T-regulatory cell balance, suppression of TLR4-MyD88, NF-κB, MAPK, and NLRP3 signaling cascades, and the influence of food matrices, microencapsulation, dosage, and processing parameters on bacterial viability and efficacy, which are the factors central to food industry application. Across models, Lactobacillus consistently down regulates pro-inflammatory Th1/Th17 responses, while expanding forkhead box protein 3 (Foxp3⁺) T reg, leading to reduced TNF-α, IL-1β, and IL-6 and elevated IL-10 and TGF-β. Short chain fatty acids (SCFAs) and indole metabolites derived from fermentation further dampen NF-κB activity and reinforce epithelial barrier function. Food matrix studies show that dairy and cereal formulations enhance probiotic survival, whereas acidic beverages often require micro encapsulation; a daily intake of ~ 10 10 CFU appears both effective and safe. Taken together, these insights position Lactobacillus as a scientifically robust, industry ready tool for developing anti-inflammatory foods, prioritizing future work for well-designed human feeding trials that couple multi-omics read outs and optimizing strain matrix combinations.

Biopesticidal activity of callus extracts of Psoralea corylifolia L. on Phenacoccus solenopsis under laboratory conditions - Sarah Ali; Saboohi Raza; Muhammad Abdul Haq; Beena Siddiqua; Syed Muhammad Zain Hashmi (International Journal of Tropical Insect Science, 2026)

Effect of storage conditions on phytochemical characteristics and activities of black tea cultivated from geographically different landscapes - Syed Ali Raza Naqvi; Sumaira Naz; Muhammad Irfan; Ameer Fawad Zahoor; Atif Hussain Randhawa; João Miguel Rocha; Mohamed Fawzy Ramadan (South African Journal of Botany, 2026)

Valorization of rubber waste for the synthesis of an acidic heterogeneous catalyst for efficient palm fatty acid distillate esterification - Muhammad Aliyu; Junaid Ahmad; Chawalit Ngamcharussrivichai; Kamil Kayode Katibi; Syed Ahmar Ali Hashmi; Umer Rashid (Process Safety and Environmental Protection, 2026)

From barns to atmosphere: Pakistan's livestock manure-derived NH3, N2O, and CH4 emissions (1961–2022) and cleaner production pathways - Syed Qasim Ali Shah; Noor Haleem; Chaudary Muhammad Haris; Leena Khan; Yousuf Jamal; Humayoun Akram; Xufei Yang (Journal of Cleaner Production, 2026)

Integrating Nanotechnology and Bioremediation for Efficient Heavy Metals Removal in Aquatic Ecosystems: A Comprehensive Review - Nadia Yasin; Syed Makhdoom Hussain; Shafaqat Ali; Ameer Fawad Zahoor; Abdulrahman Alasmari; Muhammad Munir; Muhammad Asrar; Muhammad Mudassar Shahzad; Adan Naeem (Water, Air, & Soil Pollution, 2026)

Assessment of Fine Particulate Matter (PM2.5) Induced Cyto-Genotoxicity in a Highly Polluted Urban Environment: Evidence from Lahore, Pakistan - Meerub Shazad; Muhammad Muddassir Ali; Syed Aziz ur Rehman; Maryam Javed; Jabir Hussain Syed; Asad Ullah (Water, Air, & Soil Pollution, 2026)

Phylogeny and diversity study in Damani sheep through mitochondrial DNA D-loop nucleotides sequence - Muhammad Zohaib; Farhad Ali; Syed Muhammad Suhail; Rajwali Khan; Muhammad Tariq Zeb; Ihsan Ali; Mohammad Qasim; Khalid Khan; Iftikhar Ahmad; Ijaz Ahmad (Tropical Animal Health and Production, 2026)

Inversion of Self-Potential Data from Regular Geometric Objects Using Bat Algorithms - Idrees Khan; Yi-an Cui; Muhammad Ishfaque; Syed Yasir Ali Shah (Pure and Applied Geophysics, 2026)

Virulence phenotype first: a framework for assessing the clinical risk of resistance-hypervirulence convergence in Klebsiella pneumoniae - Jiankang Zhao; Danni Pu; Muhammad Ali Syed; Rongrong Song; Yanyan Fan; Yan Liu; Bin Cao (Science Bulletin, 2026)

Unveiling the role of environmental policy stringency and informatization in shaping the e-waste landscape in Europe - Ahmed Usman; Syed Muhammad Mudassir Abbas Naqvi; Ilhan Ozturk; Ali Hassan (Journal of Environmental Chemical Engineering, 2026)

Photocatalytic CO2 reduction: Fundamental principles, mechanistic pathways and material-specific kinetic insights - Syed Izaz Ali Shah; Muhammad Anwar; Wisal Ahmad; Muhammad Ateeq; Amir Zada; Noor S. Shah; Javed Ali Khan; Changseok Han (Chemical Engineering Journal, 2026)

Paleocene stratigraphic framework and sedimentary architecture in the Sub-Himalayan Fold and Thrust Belt of Muzaffarabad, Pakistan: Depositional environment, Biotas, Paleogeographic and Economic Significance - Syed Kamran Ali; Arslan Sajjad; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Ahmer Bilal; Aamir Asghar; Aijaz Ali Halepoto; Evangelia Besiou; Assimina Antonarakou (Journal of Sedimentary Environments, 2026)

Synergistic biocontrol of Parthenium hysterophorus: the role of Curvularia specifera and Zygogramma bicolorata - Syed Muhammad Ziaullah; Muhammad Hamayun; Amjad Iqbal; Syed Asim; Sajid Ali; Anwar Hussain (Archives of Microbiology, 2026)

Green-Synthesized Gold Nanoparticles from Fortunella Margarita (Kumquat) Leaf Extract for Broad-Spectrum Antifungal Control of Postharvest Fruit Crop Pathogens - Bismillah Mubeen; Ammarah Hasnain; Haider Ali; Muhammad Nadeem Khan; Maymoona Saher; Muhammad Umer Iqbal; Syed Atif Hasan Naqvi (Applied Fruit Science, 2026)

Computational exploration of Aegle marmelos coumarins: DFT, molecular docking, and dynamics studies for anti-hypertensive activity - Jan Alam; Muhammad Ali Versiani; Nadeem Ahmed; Syed Intasar Husain Taqvi; Syed Tahir Ali; Zaheer Ul-Haq (Natural Product Research, 2026)

Spatiotemporal analysis of climatic and anthropogenic drivers of winter smog in the Indo-Gangetic Plain with a focus on Lahore - Muhammad Zeeshan Ghani; Mujtaba Hassan; Farrukh A. Chishtie; Syeda Saleha Fatim Ali; Syed Waqar Hussain Shah; Ahmad Bilal (Environmental Science and Pollution Research, 2026)

The role of MXene interfaces in decoupling electronic and thermal transport in Bi2Te3 composites - Samira Saddique; Inaam Ullah; Syed Zuhair Abbas Shah; Ayesha Irfan; Nimra Irshad; Muhammad Irfan; Shanza Taswar; Salamat Ali; Muhammad Amer Mustafa; Guiying Xu (Chemical Engineering Journal, 2026)

Optimum N Fertilization Enhances Salinity Tolerance and N use Efficiency in Maize through Modulation of Antioxidant Defense and Biochemical Pathways - Syed Ayyaz Javed; Muhammad Tauseef Jaffar; Muhammad Ashraf; Muhammad Ahmed; Ali Raza Siddiqui; Hafiz Muhammad Bilal; Jawad Amin; Sanaullah Sattar (Journal of Plant Growth Regulation, 2026)

Retraction Note: Therapeutic Potential of Aloe vera and Aloe vera–Conjugated Silver Nanoparticles on Mice Exposed to Hexavalent Chromium - Tooba Nauroze; Shaukat Ali; Shagufta Andleeb; Chaman Ara; Iqra Liaqat; Hina Mushtaq; Samaira Mumtaz; Lubna Kanwal; Afshan Syed Abbas; Shumaila Mumtaz; Muhammad Adeel Farooq; Istaqlal Hussain Khan (Biological Trace Element Research, 2026)

Chemical contaminants and fish: implications for health and ecosystem sustainability - Muhammad Sohail; Mohammad Ali Nematollahi; Sardar Suleman; Syed Sikandar Habib (Environmental Monitoring and Assessment, 2026)

Antimicrobial and antioxidant activities of Tetracera macrophylla Hook.f. & Thomson leaf extracts: insights from Q-ToF-LCMS, pharmacokinetics and molecular docking approach - Qamar Uddin Ahmed; Muhammad Akmal Hakim Ab Rahim; Mohd Hafiz Arzmi; ABM Helal Uddin; Syed Adnan Ali Shah; Mohd Salleh Rofiee; Humaira Parveen; Sayeed Mukhtar; Uzma Faridi; Nurul Hidayah Mohd Rosedi; Murni Nazira Sarian; Taslima Begum (Natural Product Research, 2026)

Network pharmacology and molecular docking reveal PPARγ-directed antidiabetic phytochemical compounds of Momordica charantia - Owais; Israr Hussain; Muhammad Rahiyab; Arshad Iqbal; Syed Shujait Ali; Mohamed Taha Yassin (In Silico Pharmacology, 2026)

Data-driven explainable artificial intelligence models for predicting CO2 uptake in metal–organic frameworks - Mohd Azfar Shaida; Laiba Saleem; Syed Ali Waqas Ahmad; Saad Shamim Ansari; Syed Muhammad Ibrahim (Environmental Science and Pollution Research, 2026)

Comparative analysis of machine learning and neural network models for petrophysical property prediction in heterogeneous reservoirs - Zayan Khursheed; Muhammad Anas Jawaid; Muhammad Mustafa; Shaine Mohammadali Lalji; Syed Imran Ali; Mohsin Ayubi (Next Research, 2026)

Performance assessment of nature-based solutions for sustainable urban housing - Muhammad Aarish Shah; Syed Hassaan Ali Shah; Omama Zeb; Aman Alam (Energy and Buildings, 2026)

Integrating CMIP6 climate projections with community-based vulnerability assessment for climate resilience in Haripur, Pakistan - Syed Shujaat Ali; Sabahat Isha; Hamza Paracha; Abdullah Nadeem; Muhammad Atiq Ur Rehman Tariq (Theoretical and Applied Climatology, 2026)

Formulation Design of Glucuronoxylan-Based Stimuli-Responsive Microparticles for Zero-Order Drug Delivery - Saleha Babar; Fatima Akbar Sheikh; Syed Nasir Abbas Bukhari; Muhammad Tahir Haseeb; Arshad Ali; Nisar Ul Khaliq; Ranya Abdulrahman Alafar; Mohamed Abdelwahab Abdelgawad; Ameeduzzafar Zafar; Naveed Ahmad (Journal of Pharmaceutical Innovation, 2026)

Integrated computational, pharmacological and molecular investigations of piperitone in mitigating Alzheimer disease pathology by targeting cholinesterases, β-secretase and neuroinflammation - Rubia Anwer; Ihsan Ullah; Arif-ullah Khan; Mushtaq Ahmad Mir; Nasreena Bashir; Syed Uzair Ali Shah; Muhammad Ayaz (Inflammopharmacology, 2026)

Limitations in Assessing Torsades de Pointes Risk in a Swedish Population Based Study - Zubaida Bibi; Syed Muhammad Rayyan; Kausar Ali (European Journal of Clinical Pharmacology, 2026)

Mineral chemistry and alteration characteristics of sulfide-bearing metavolcanics in the Thalle area, Kohistan–Ladakh Arc: insights into magmatic-hydrothermal fluid evolution - Muhammad Farhan; Tehseen Zafar; Mohammad Arif; Chun-Feng Li; Zahid Hussain; Zaheen Ullah; Syed Wajid Hanif Bukhari; Uzair Siddique; Syed Ali Turab; Mubasir Ali (Geosciences Journal, 2026)

Harnessing novel biosynthesized ZrO₂ biochar nanocomposites for reactive orange 16 dye adsorption: kinetic modeling and cytotoxicity insights - Mubashara Fayyaz; Mohamed A. Habib; Syed Kashif Ali; Saif Ullah; Muhammad Imran Kanjal; Tahreem Saleem; Rana Muhammad Zulqarnain; Ahmed B. M. Ibrahim (Biodegradation, 2026)

Improving Wheat Production in Pakistan Through an Economically Viable Solar‐Powered Rain Gun Sprinkler Irrigation System - Muhammad Asif; Shahzad Hussain Dahri; Bashir Ahmad; Noman Latif Sadozai; Sohail Raza Haidree; Abdul Hannan; Syed Qasim Ali Naqvi (Irrigation and Drainage, 2026)
In rainfed agriculture, limited water availability has become a challenging factor for sustainable farming and economic security. For regions with variable climate conditions, efficient water management practices must be adopted to improve livelihoods and food security. This study aimed to evaluate the role of supplemental irrigation for wheat crops in the Pothwar region. The irrigation management consists of I 0 (rainfed), I 1 (10 mm presowing), I 2 (10 mm at 50% soil moisture depletion [SMD]) and I 3 (25 mm at 75% SMD). The results revealed that, under I 3 , the grain yield increased by 49% and 17%, followed by I 2 (47% and 12%) compared to the rainfed yield of 1.85 and 3.93 tons/ha in Jand and NARC, respectively. The analysis of variance and Tukey's honestly significant difference (HSD) test revealed that the yield for I 0 value was significantly lower than that of all the irrigation treatments, while there were no significant differences among I 1 , I 2 and I 3 . The net benefit analysis revealed that I 3 was an economic irrigation schedule and paid back the total intervention cost by generating PKR 389,915/ha at NARC and PKR 283,915/ha at Jand in 3.83 and 4.93 years, respectively. This viable economic return makes solar‐powered irrigation systems reliable sources of water for water‐scarce and climate‐variable regions.

Mechanical power for ventilation - looking beyond the lung - Mutaz I. Othman; Majd M. AlBarakat; Ahmed S. Mohamed; Syed Muhammad Hassan; Rebecca R. George; Ahmad A. Omari; Emad M. Mustafa; Ali Ait Hssain; Hana J. Abukhadijah; Abdulqadir J. Nashwan (Next Research, 2026)

Detection and serotyping of bluetongue viruses in Khyber Pakhtunkhwa Province, Pakistan - Muhammad Ishaq; Syed M. Jamal; Syed Asad Ali Shah; Hanif Ur Rahman; Alessandra Leone; Liana Teodori; Maura Pisciella; Ottavio Portanti; Cesare Cammà; Valentina Curini; Maurilia Marcacci; Barbara Secondini; et al. (Tropical Animal Health and Production, 2026)

The gut–liver–virus axis in hepatitis B and C: microbiota, immunometabolism, and exosome-mediated therapeutic opportunities - Kainat Raziq; Syed Qaswar Ali Shah; Mirza Naveed Shahzad; Umm E. Ummara; Mishal Subhan; Muhammad Muzammil Nazir (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Efficient De Novo Assembly and Recovery of Microbial Genomes from Complex Metagenomes Using a Reduced Set of k-mers - Hajra Qayyum; Muhammad Faheem Raziq; Haseeb Manzoor; Syed Shujaat Ali Zaidi; Amjad Ali; Masood Ur Rehman Kayani (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Reservoir characterization for hydrocarbon assessment of Eocene carbonates in Meyal area, Potwar Plateau, Pakistan: implications from geophysical logs data - Yasir Hamid; Muhammad Kamran; Syed Mamoon Siyar; Saqib Mehmood; Taqweem Ul Haq Ali; Fayaz Ali; Ibrar Ul Haq; Izhar Ullah; Kamran Shams; Sartaj Husain (Carbonates and Evaporites, 2026)

Genomic surveillance of Influenza, SARS-CoV-2, and RSV in patients from Islamabad and Rawalpindi, Pakistan: a 2023-24 perspective - Zunera Jamal; Syed Adnan Haider; Fahad Humayun; Qasim Ali; Rabia Hakim; Muhammad Salman; Massab Umair (Archives of Virology, 2026)

Calocybe barangensis sp. nov (Lyophyllaceae), from Bajaur, Pakistan - Mohsin Ullah; Malka Saba; Dege Zheng; Umer Rehman; Muhammad Asif; Syed Mohammad Tauseeq Ali Shah; Dong‐Qin Dai; Ishtiaq Ahmad; Samantha C. Karunarathna (New Zealand Journal of Botany, 2026)
In this study, we report a new taxon, Calocybe barangensis , from Barang, Bajaur District, Khyber Pakhtunkhwa, Pakistan. The species was described as new to science using molecular phylogenetic analysis of combined ITS and LSU datasets, as well as comparisons of its macro‐ and micromorphological characteristics with those of similar taxa. The new species forms a separate clade in the phylogenetic tree and differs in having small basidiomata with dark yellowish‐brown spores and large, globose to subglobose basidiospores (5.9–7.2 × 4.7–5.6 μm). A full description, illustrations, and phylogenetic analysis results of the new species are provided.

YOLO-based real-time floating debris counting in urban rivers for flood monitoring and water resource management - Shaufikah Shukri; Latifah Munirah Kamarudin; Azfar Haniff Zuel Azwar; Noraini Azmi; Ammar Zakaria; Ahmad Shakaff Ali Yeon; Syed Muhammad Mamduh Syed Zakaria; Retnam Visvanathan (Environmental Monitoring and Assessment, 2026)
Urban flooding is increasingly exacerbated by the accumulation of floating debris in rivers, which obstructs water flow, degrades water quality, and poses significant risks to human safety and environmental sustainability. Effective monitoring of floating debris is therefore critical for early flood warning and long-term water resource management. This study presents a real-time monitoring framework that integrates deep learning-based object detection models, You Only Look Once (YOLO) with video surveillance for the identification and quantification of floating debris in urban rivers. Field deployments were conducted in flood-prone sites in Shah Alam, Malaysia, to evaluate the system under real-world environmental conditions. Results show that YOLOv7 achieved higher accuracy and robustness across diverse debris classes and lighting conditions compared to YOLOv9, with precision, recall, and F1-scores demonstrating strong detection reliability. Beyond technical accuracy, the system provides timely and actionable information for flood risk assessment, river management, and environmental monitoring. By automating debris detection and quantification, this study contributes to Sustainable Development Goals (SDGs) 11 (Sustainable Cities and Communities) and 13 (Climate Action), offering a scalable monitoring solution for flood-prone regions.

Network pharmacology and molecular dynamics based elucidation of Mentha piperita phytochemicals in colorectal cancer therapy - Ruqia Sartaj; Itazaz Ul Haq; Haleema Sartaj; Muhammad Rahiyab; Abbas Khan; Israr Hussain; Li Pinyi; Muhammad Rizwan; Syed Shujait Ali; Arshad Iqbal (In Silico Pharmacology, 2026)

Enhancing transgender mobility on public transport through equitable transport policies in a culturally conservative society - Nazam Ali; Muhammad Ashraf Javid; Ryan Cheuk Pong Wong; Muhammad Abdullah; Syed Sift-E-Hassan; Punyaanek Srisurin; Qudeer Hussain (Journal of Transport Geography, 2026)

Comprehensive assessment of hydrogen jet dynamics under split-injection conditions - Youngmin Ki; Syed Muhammad Sameh Ali; Jinsu Kim; Joonsik Hwang; Choongsik Bae (Fuel, 2026)

Synergistic effects in FeP4-NPC-CP Nanocomposites electrocatalysts for Boosted nitrate reduction to ammonia - Ya-Fei Guo; Sajid Mahmood; Anum Bilal; Ali Bahadur; Shahid Iqbal; Ali Hussain; Muhammad Sajjad; Syed Kashif Ali; Salah Knani (Fuel, 2026)

Antibacterial Activity of Anthraquinones Isolated from Reynoutria Japonica Against Staphylococcus aureus: An in Silico and In Vitro Approach - Iqra Anam Khawaja; Sajid Ali; Muhammad Faheem; Syed Babar Jamal; Adnan Haider; Falak Niaz; Mi-Jeong Ahn; Mutiullah Khattak; Atif Ali Khan Khalil (Journal of Pharmaceutical Innovation, 2026)

Developing a RUSLE-Based Tool for Analyzing Climate Induced Soil Erosion and Reservoir Sedimentation in the Tarbela Region - Muhammad Arif Goheer; Sher Shah Hassan; Syeda Rosheen Raza Kazmi; Muhammad Taimoor Ashfaq Malik; Syed Zee Ali Shan (International Journal of Environmental Research, 2026)

Electron-rich sulfur sites and dual interfacial bonds in S-scheme heterojunction enable high quantum yield and stable hydrogen production - Sharafat Ali; Sajjad Ali; Shu-Long Li; Ahmed Ismail; Sher Ali; Pir Muhammad Ismail; Syed Ul Hasnain Bakhtiar; Fazal Raziq; Mohammad Z. Rahman; Liang Qiao (Chemical Engineering Journal, 2026)

Seed Priming with Osmolytes Ameliorates Salinity Tolerance in Maize (Zea mays L.) Through Embryonic Modifications - Paris Riaz; Ansa Asghar; Sana Fatima; Sana Basharat; Zahida Parveen; Mansoor Hameed; Farooq Ahmad; M. Sajid Aqeel Ahmad; Muhammad Ashraf; Faakeha Islam; Syed Mohsan Raza Shah; Qasim Ali (Journal of Plant Growth Regulation, 2026)

Bentonite clay in aflatoxin mitigation: advances, efficiency and perspectives - Syed Ali Raza Naqvi; Muhammad Kaleem Khan Khosa; Ameer Fawad Zahoor; Matloob Ahmad; Ariba Abdullah; Muhammad Ramzan Saeed Ashraf Janjua; Syed Ansar Abidi; Fatma Mohamed Ameen Khalil; Mohamed Fawzy Ramadan; João Miguel Rocha (Archives of Microbiology, 2026)

Unlocking geothermal potential in abandoned hydrocarbon and exploration wells: a sustainable energy solution - Muhammad Affan Uddin Ali Khan; Syed Imran Ali; Shaine Muhammadali Lalji; Aliza Hussain; Wajih Hasan; Munira Akhtar Khan; Syed Danish Rasool (Arabian Journal of Geosciences, 2026)

The Intricate Role of Caspase-6 and Death Receptor-6 in Neurodegenerative Diseases - Ali Zulqarnain; Muhammad Ukasha; Syed Zahid Ali Shah (Cell Biochemistry and Biophysics, 2025)

From genes to fields: Genetic determinants and tillage practices shaping cereal root systems for sustainable productivity - Asad Azeem; Sami Ul-Allah; Sana Khan; Muhammad Zia Ul Haq; Muhammad Sikandar Zaman; Syed Ali Murtaza Gallani (Rhizosphere, 2025)

Biphasic synthesis of Pd/Ovs-TiO₂ (black) for efficient moxifloxacin degradation and toxicity mitigation - Muhammad Imran Kanjal; Iram Yasmin; Syed Kashif Ali; Muhammad Wasim Afzal; Muhammad Irfan Ahamad; Mohamed A. Habib; Ahmed B.M. Ibrahim; Rana Muhammad Zulqarnain (Journal of Water Process Engineering, 2025)

Effect of dietary proteins on mayonnaise techno-functionality and rheology: A review - Wahab Ali Khan; Muhammad Waseem; Iqra Yasmin; Syed Abdul Wadood; Aiza Qamar; Muhammad Rizwan Javed; Muhammad Saleem; Crossby Osei Tutu (Food and Humanity, 2025)

Engineering multifunctional fire proof superhydrophobic cotton fabric via sequential coating of flower-like PPPA/BMOF and PDMS - Tooba Ali; Naseer Ahmad; Waqas Ahmad; Hua-Ming Xiao; Syed Muhammad Jawad; Muhammad Imran Malik; Dilshad Hussain (Chemical Engineering Journal, 2025)

Toxic Metals in the Workplace: Assessing Heavy Metal Contaminants in Indoor Dust of Auto Parts Stores and Their Impact on Health of Employees - Nadeem Ali; Sultan H. Alamri; Jahan Zeb; Mohammad Rehan; Nisreen Rajeh; Nabil Alhakamy; Mohamed I. Orif; Muhammad Imtiaz Rashid; Syed Ali Musstjab Akber Shah Eqani; Hani Z. Asfour (Water, Air, & Soil Pollution, 2025)

Ameliorative effects of Ocimum sanctum in Oreochromis niloticus against waterborne sub-lethal cadmium toxicity - Muhammad Attaullah Saad; Syed Makhdoom Hussain; Shafaqat Ali; Abdul Ghafoor; Syed Zakir Hussain Shah; Abdulrahman Alasmari; Anam Khalid (Veterinary Research Communications, 2025)

The weight reducing effects of naltrexone-bupropion among obese psychiatric and non-psychiatric patients: a systematic review - Hafsah Alim Ur Rahman; Muhammad Ahmed Ali Fahim; Unaiza Naeem; Syed Hassan Ahmed; Muhammad Youshay Jawad; Hareem Arshad; Anil Kalyoncu; Mujeeb U. Shad; Ahmad Hameed (Psychopharmacology, 2025)

Variations in Wheat and Soil N Concentration by the Sole and Combined Foliar Application of NPK and Humic Acid Levels - Khadim Dawar; Shahid Ali; Ibad Ullah; Ishaq Ahmad Mian; Bushra Khan; Muhammad Tariq; Aamir Khan; Syed Sartaj Alam; Muhammad Mudasar Malik (Journal of Soil Science and Plant Nutrition, 2025)

Carbon Nanotubes Improve Quantitative and Qualitative Attributes of Potato (Solanum tuberosum L) Genotypes - Muhammad Ismail; Muhammad Imtiaz; Raham Sher Khan; Fazal Jalal; Fazal Said; Muhammad Ali Khan; Syed Hussain; Badshah Islam; Salman Khan; Sabir Khan; Atta Ullah; Maqsood Khan; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Consortium of Endophytic Bacillus australimaris CK11 and Staphylococcus epidermidis CK9 from Commiphora gileadensis Mediates Tomato Resilience to Combined Salinity, Heat, and Drought Stresses - Syed Saad Jan; Nasir Ali Khan; Sajjad Asaf; Raheem Shahzad; Lubna; Muhammad Imran; Saqib Bilal; In-Jung Lee; Ahmed Al-Harrasi (Journal of Plant Growth Regulation, 2025)

Spatial Distribution, Characterization and Ecological Risk Assessment of Microplastic Pollution in Different Environmental Matrices of River Ravi, Pakistan - Sara Shamshad; Safdar Sidra; Asia Iqbal; Aamna Ishaq; Afzal Nimra; Muhammad Muddassir Ali; Syed Ghulam Mohayud Din Hashmi; Muhammad Rashid; Fariha Arooj; Abdul Qadir; Rida Ahmad; Zulfiqar Ali (International Journal of Environmental Research, 2025)

Green Synthesis of Mangifera Indica Mediated NiO and NiMn2O4 Nanomaterials for Electrocatalytic Water Splitting - Fatima Masood; Shabbir Hussain; Muhammad Arif; Shahzad Murtaza; Muhammad Imran; Muhammad Bilal Tahir; Khurram Shahzad Munawar; Hamad M. Alkahtani; Amer Alhaj Zen; Syed Adnan Ali Shah (International Journal of Environmental Research, 2025)

Exploring the therapeutic potential of Nasturtium microphyllum (Boenn.) Rchb.: a combined in-vitro, in-vivo and in-silico approach - Rabia Khan; Muhammad Musa; Syed Mubassir Shah; Hussan Ara Begum; Alaa S. Alhegaili; Sajid Hussain; Atif Ali Khan Khalil; Sajid Ali (Inflammopharmacology, 2025)

Exploration of medicinal and nutritional value of Himalayan wild edible fruits: implications for sustainable health and functional foods - Syeda Khateeb Fatima; Rizwan Taj Khan; Munazza Nazir; Muhammad Manzoor; Syed Waseem Gillani; Mumna Munir; Muhammad Nasir; Wasim Akhtar; Shabir Ahmad; Manal Abdulaziz Binobead; M Ajmal Ali (Genetic Resources and Crop Evolution, 2025)

Nutlet micromorphology and systematic implications of genus Nepeta (Lamiaceae): correct taxonomic tool for taxa identifications - Shaista Jabeen; Mushtaq Ahmad; Muhammad Zafar; Shabir Ahmad; Hussain Shah; Ateef Ullah; Syed Waseem Gillani; Muhammad Manzoor; Ashraf M. M. Abdelbacki; Ali M. Sayed (Genetic Resources and Crop Evolution, 2025)

Genomic Insights into Poultry-Associated Staphylococcus Aureus from Haripur, Pakistan - Arif Ullah; Bushra Fatima; Mohammad Ejaz; Muhammad Ali Syed (Current Microbiology, 2025)

Sedimentology and biostratigraphy of the Cretaceous–Paleocene successions in Northern Pakistan: evidence from the Hazara, Kala Chitta, Potwar, and Kohat Basins - Syed Kamran Ali; Hafiz Sohaib Bashir; Asim Qadir; Muhammad Saleem Mughal; Khurram Iqbal; Abrar Niaz; Khawaja Umair Majeed (Carbonates and Evaporites, 2025)

Dolomitized stromatolites during regressive-transgressive cycles in the Cambrian Abbottabad Formation, Pakistan: depositional environment, sequence stratigraphic significance, and paleogeographic implications - Syed Kamran Ali; George Kontakiotis; Tariq Mahmood; Muhammad Saleem Mughal; Hammad Tariq Janjuhah; Ahmer Bilal; Evangelia Besiou; Assimina Antonarakou (Carbonates and Evaporites, 2025)

Optimizing aquaculture sustainability: Microalgae-based co-culture systems for aquaculture wastewater treatment and pollution reduction - Javaeria Maqsood Gill; Syed Makhdoom Hussain; Shafaqat Ali; Ameer Fawad Zahoor; Abdulrahman Alasmari; Muhammad Munir; Eman Naeem; Muhammad Amjad; Zeeshan Yousaf; Muhammad Faisal (Algal Research, 2025)

Remedial effects of fenugreek seed extract against tannery effluent toxicity on the growth, blood profile, immune response, and antioxidant activity in Labeo rohita - Muhammad Amjad; Syed Makhdoom Hussain; Salma Sultana; Shafaqat Ali (Aquaculture International, 2025)

Magnetic MOF-Based Immunosensing Strategy with Quantum Dot Labeling for Efficient Electro-chemiluminescent Detection of Alpha-fetoprotein - Mariyam Fatima; Muhammad Faizan; Iqra Jabeen; Muhammad Fiaz; Ansar Ali; Syed Kashif Ali; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Ibrahim Jafri; Abd-ElAziem Farouk (Journal of Fluorescence, 2025)

Quinic acid and its derivatives protect against phytohaemagglutinin-induced Alzheimer's-like neurotoxicity in SH-SY5Y cells by down-regulating p38 MAPK signaling pathway - Kinza Rafi; Shaheen Faizi; Syed Saad Hussain; Shumaila Shamshad; Muhammad Ali Versiani; Shabana U. Simjee (Toxicology and Applied Pharmacology, 2025)

Occurrence and molecular characterization of root-knot nematodes on tunnel-grown cucumber (Cucumis sativus) in Balochistan province of Pakistan - Syed Shams Ullah; Amjad Abbas; Muhammad Dildar Gogi; Shahid Siddique; Muhammad Amjad Ali (Physiological and Molecular Plant Pathology, 2025)

DFT, GC-MS analysis and biological evaluation of Limbarda crithmoides L. Dumort essential oil; an important edible halophyte grown in Pakistan - Muhammad Iltaf; Shah Iram Niaz; Muhammad Kashif Majeed; Muhammad Saleem; Mubarak Shah; Muhammad Ali; Syed Shakeel Abbas; Adnan Amin (Natural Product Research, 2025)

Potential of Organic Amendments as a Sustainable Strategy to Enhance Rice Yield by Improving Nutrient Use Efficiency and Physiological Performance in Alkaline Soil - Muhammad Ahmed; Muhammad Tauseef Jaffar; Zulfiqar Ahmad; Muhammad Naveed; Syed Ayyaz Javed; Muhammad Shoaib Asad; Ali Raza; Awais Shakoor; Jianguo Zhang (Journal of Plant Growth Regulation, 2025)

Structure-guided drug repurposing and dynamics simulation reveal anti-viral candidates for Bourbon virus - Israr Hussain; Itazaz Ul Haq; Muhammad Rahiyab; Junaid Khan; Rooh Ullah; Syed Shujait Ali; Hassan Sher; Arshad Iqbal (In Silico Pharmacology, 2025)

Fluoride contamination of groundwater in different geological settings of Punjab Province, Pakistan: Levels, possible mechanisms and health risks - Muhammad Sadiq; Syed Ali Musstjab Akber Shah Eqani; Ismat Nawaz; Nazneen Bangash; Shazia Ilyas; Joel Podgorski; Michael Berg (Science of The Total Environment, 2025)

An effective bi-functional electrocatalyst for electrochemical water splitting using NiCo2O4 nanoparticles decorated with Polypyrrole nanocomposite - Khadija-Tul-Kubra; Faiqa Noreen; Ali Junaid; Atif Nazir; Sehrish Arshad; Komal Bibi; Ayesha Batool; Aleeza Sattar; Aboud Ahmed Awadh Bahajjaj; Sohail Ahmad; Muhammad Shuaib Khand; Syed Imran Abbas Shah (Fuel, 2025)

Tuning water transport channels in sulfonated copolymer membranes for highly effective removal of arsenic and selenium from industrial wastewater - Syed Qamber Ali Zaidi; Muhammad Hafi Wadgama; Zaib Jahan; Muhammad Bilal Khan Niazi; Faheem Hassan Akhtar (Desalination, 2025)

Carbon-negative process Integration: Techno-economic framework for biomass-blend bio-energy carbon capture and storage polygeneration with high-value co-product streams - Syed Muhammad Mustafa Rizvi; Bilal Kazmi; Syed Ali Ammar Taqvi; AbdulAziz AlGhamdi (Biomass and Bioenergy, 2025)

Silicic acid seed pre-treatment modulates growth and antioxidant responses in maize under drought stress - Abid Ali; Sara Zafar; Kashf Mehmood; Zuhair Hasnain; Muhammad Nawaz; Syed Muhammad Junaid Jalal Gilani; Manzer H. Siddiqui; Saud Alamri; Shahbaz Khan (The Science of Nature, 2025)

Epigenetic horizons in aquaculture: unlocking sustainable fish production - Khalid Hussain; Syed Makhdoom Hussain; Shafaqat Ali; Ameer Fawad Zahoor; Ebru Yilmaz; Abdulrahman Alasmari; Muhammad Munir; Muhammad Zubair-ul-Hassan Arsalan; Adan Naeem (Fish Physiology and Biochemistry, 2025)

Preliminary Detection of Bats-associated Influenza A virus from Pakistan - Sidra Rahman; Syed Ahsan Shahid; Hassan Ayaz; Sajid Ali Shah; Muhammad Ali (Current Microbiology, 2025)

Debris flow susceptibility and propagation modeling: a deep learning and flow-R framework - Muhammad Khalid; Muhammad Zulkarnain bin Abd Rahman; Jabir Hussain Syed; Nafees Ali; Hamza Daud; Muhammad Afaq Hussain; Muhammad Safwan Ruslan; Omar Farouk Fauzi (Bulletin of Engineering Geology and the Environment, 2025)

Using immunoinformatics and bioinformatics approach to design novel and effective rational in-silico vaccine against human Astrovirus targeting the capsid polyprotein VP90: a silent threat to global gastrointestinal tract - Itazaz Ul Haq; Najeeb Ullah; Muhammad Rahiyab; Ruqia Sartaj; Ishaq Khan; Syed Shujait Ali; Fazal Akbar; Arshad Iqbal (In Silico Pharmacology, 2025)

Bay leaves: the neuroprotective dietary spice via inhibition of amyloid-like aggregation - Nazish Mustafa; Sana Khan; Laila Anwar; Mir Muhammad Uzairullah; Huma Aslam Bhatti; Syed Abid Ali; Ghulam Abbas (Metabolic Brain Disease, 2025)

Blue carbon management integrating socioeconomic and environmental interconnectivity in Southeast Asia: an urgent climate priority - Amani Becker; Sarah K. Bercovici; Jenny Choo; Fakhrurrozi Fakhrurrozi; Annabelle Fong; Sara E. Fowell; Emmy Hossain; Muhammad Ali Syed Hussein; Maryam Jamilah; Aazani Mujahid; Moritz Müller; Jillian Lean Sim Ooi; et al. (Frontiers in Marine Science, 2025)
This perspective article synthesises insights from a 2023 interdisciplinary workshop in Kuching, Malaysia, where 26 experts examined how land use and land cover change (LULCC) impacts Blue Carbon Ecosystems (BCE) in Southeast Asia (SEA) and identified pathways for integrated, science-informed governance. BCE in SEA (mangroves, seagrasses and tidal wetlands) are globally significant carbon sinks, critical to biodiversity and the livelihoods of millions, dependant on them for food, income and coastal protection. Yet rapid development and socio-economically driven LULCC threaten BCE resilience and carbon storage capacity. Blue Carbon initiatives risk falling short if they overlook the socio-ecological interconnectivity of these systems. Advances in remote sensing, sediment carbon accounting and ecosystem modelling have improved BCE monitoring, but key gaps persist. These include understanding cumulative upstream effects of LULCC on BCE carbon dynamics, integrating socio-economic with ecological data for robust scenario modelling and evaluating governance effectiveness and equity over time. We frame BCE as dynamic, interconnected socio-ecological systems and call for the advancement of systems thinking in coastal and climate policy. We underscore the need for transdisciplinary, nested governance models operating across ecological scales and political boundaries and argue for a systems-based management approach that links land-sea processes, addresses upstream-downstream dynamics and balances carbon market incentives with local needs. Recommendations include improved monitoring and carbon accounting; alignment between science and policy; regionally coordinated governance; and diversifying finance to reflect the full value of BCE beyond carbon. Together, these actions chart a path for resilient, science-based, socially inclusive BCE conservation in SEA.

Petrological and Re-Os isotopic constraints on the origin of chromitites and peridotites of the late cretaceous Waziristan ophiolite, western Pakistan: implications for subduction initiation - Zaheen Ullah; Asad Khan; Huan Li; Scott A. Whattam; Muhammad Tahir Shah; Liaqat Ali; Shah Faisal; Tehseen Zafar; Muhammad Farhan; Shuja Ullah; Syed Tanvir Shah; Zahid Hussain; et al. (International Geology Review, 2025)

Polymeric carbon nitride-based semiconductors as a beneficial candidate in photocatalysis diversity: A comprehensive review - Sidra Tul Muntaha; Jawad Ali Shah Syed; Muhammad Mateen; Muhammad Ali Shahzad; Anand Parkash; Aqsa Asrar; Adil Emin; Ghulam Abbas Ashraf; Inaam Ullah; Muhammad Ahsan Farooq Qaisar; Salamat Ali; Ahmed Mahmoud Idris (Chemical Engineering Journal, 2025)

Advancing algae-based Bioenergy: Techno-Economic assessment of hydrogen and biochar production from algal biomass - Aliyan Tanweer; Syed Ali Ammar Taqvi; Bilal Kazmi; Safiya Khatoon; Muhammad Taha; Muhammad Nadir; Farooq Ahmad; Naveed Ahmad (Biomass and Bioenergy, 2025)

Phosphorus Modified Biochar and Vermicompost Integration Alleviated Cd Phytotoxicity in Wheat (Triticum aestivum L.) by Improving Growth, Antioxidant Activities and Reducing Cd Uptake in Plants - Ahmad Ali; Zaffar Malik; Ghulam Hassan Abbasi; Muhammad Waseem; Muhammad Rizwan; Muhammad Ali; Sobia Afzal; Syed Farhan Haider Bukhari; Usama Ali Tahir (Journal of Soil Science and Plant Nutrition, 2025)

Unlocking the Geoheritage Potential of Hingol National Park (HNP), Pakistan: Geological and Geomorphological Insights Through Multi-Satellite Remote Sensing Data and Field Geology Validation - Muhammad Yaseen; Rujun Chen; Jawad Ahmad; Shahid Ali Shah; Shah Fahad; Muhammad Naveed Anjum; Syed Tanvir Shah (Geoheritage, 2025)

Fracture analysis and reservoir potential of Jurassic-Paleocene rocks exposed in lower Orakzai area, Lesser Himalayas, Pakistan - Wasif Ullah; Syed Ali Turab; Muhammad Awais Aziz; Nasar Khan (Carbonates and Evaporites, 2025)

Metabolic Heat Output of Chondrocytes: Implications for Joint Degeneration in Osteoarthritis - Ayesha Parvaiz Malik; Amna Pervez Malik; Javed Iqbal; Brijesh Sathian; Syed Muhammad Ali (Annals of Biomedical Engineering, 2025)

An integrated evaluation framework for evaluating renewable-based building sector implementation in remote/off-grid areas with varying climatic zones - Rida Maryam; Syed Ali Abbas Kazmi; Muhammad Hassan; Mustafa Anwar (Energy and Buildings, 2025)

Gallic acid alleviates omeprazole-induced depressive behavior and memory impairment - Noreen Samad; Natasha Manzoor; Ali Irfan; Arslan Khalid; Umer Ejaz; Bakar Bin Khatab Abbas; Syed Aun Muhammad; Gamal A. Shazly; Saima Khaliq; Yousef A. Bin Jardan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Macroalgae Polysaccharides Enhance Brain Health by Mitigating Scopolamine-induced Oxidative Stress and Inflammation Via Nrf-2/TLR4/NF-kB Pathways - Zahir Shah; Arshad Iqbal; Syed Lal Badshah; Mushtaq Ahmad Mir; Saima Sohni; Hammad Ullah; Shahid Ali Shah; Nasreena Bashir; Muhammad Ayaz; Maria Daglia (Journal of Neuroimmune Pharmacology, 2025)

Breakthrough in plasmonic enhanced MOFs: Design, synthesis, and catalytic mechanisms for various photocatalytic applications - Waqar Ahmad Qureshi; Syed Najeeb-Uz-Zaman Haider; Muhammad Adnan Qaiser; Shahid Khan; Weikang Wang; Rai Nauman Ali; Amjad Ali; Ahmad Naveed; Mohamed Hussein Abdurahman; Muhammad Usman Khan; Muhammad Tayyab; Lele Wang; et al. (Environmental Research, 2025)

A remote sensing and GIS-based analysis of forest cover changes and carbon sequestration trends over three decades - Ali Raza; Neyha Rubab Syed; Romana Fahmeed; Siham Acharki; Sajjad Hussain; Muhammad Zubair; Dinesh Kumar Vishwakarma; Arpit Gaur; Bhaskar Pratap Singh; Abdelaziz M. Okasha; Ahmed Z. Dewidar; Mohamed A. Mattar (Environmental Development, 2025)

Cadmium Toxicity Affects Morpho-Physiological and Biochemical Attributes in Gladiolus grandiflorus L.: The Mitigating Roles of Exogenous Strigolactone (GR24) - Muhammad Ahsan; Muhammad Abdullah; Emanuele Radicetti; Mohamed Farouk Elsadek; Ali Bakhsh; Mateen Sajid; Mohammad Valipour; Aftab Jamal; Hera Gul; Syed Mohsin Abbas (Water, Air, & Soil Pollution, 2025)

Comparative efficacy of combined myo-inositol and D-chiro inositol versus metformin across PCOS Phenotypes: enhancing ovarian function, ovulation, and stress response in a prospective clinical trial - Meena Gul; Hina Khan; Bushra Rauf; Syed Murtaza Shah Bukhari; Ehtesham Ehtesham; Muhammad Omar Malik; Fawad Ali Shah; Fawaz E. Alanazi; Mohsin Shah (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Towards sustainable methanol production: energy, exergy, economics, and environmental evaluation of Thar coal gasification - Syeda Asra Arshad; Umna Nasir Ali; Syed Ali Ammar Taqvi; Bilal Kazmi; Ahsan Khalid; Muhammad Ahmer; Farooq Ahmad; Naveed Ahmad (Environment, Development and Sustainability, 2025)

Molecular modeling to design a multiepitope vaccine against emerging tick-borne Yezo virus and its validation through biophysics techniques - Hassan Ayaz; Muhammad Suleman; Asad Ali Shah; Syed Ainul Abideen; Faisal Ahmad; Muhammad Ali; Sajjad Ahmad; Asia Nawaz; Hanbal Ahmad khan; Inam Hussain; Muhammad Irfan; Yasir Waheed (In Silico Pharmacology, 2025)

Advanced characterization of hemp biomass pyrolysis: Bioenergy recovery and environmental implications - Rashid Minhas; Asif Hussain Khoja; Hajirah Kanwal; Muhammad Hassan; Arslan Khan; Syed Sheraz Daood; Israf Ud din; Ali Bahadar (Sustainable Chemistry and Pharmacy, 2025)

Development and techno-economic analysis of an innovative solar-based ammonia synthesis system - Zihan Lin; Muhammad Sajid Khan; Saboora Khatoon; Shuiqing Zhou; Weiya Jin; Muhammad Abid; Syed Waqas Hussain Shah; Chen Chen; Ali Ahmed Alqahtani (Process Safety and Environmental Protection, 2025)

Petrogenesis and tectonic implications of Paleozoic S-type granitic gneisses of Nanga Parbat Syntaxis, North Pakistan - Amjad Hussain; Kui-Dong Zhao; Delores M. Robinson; Sakine Moradi; Muhammad Sajid; Hafiz U. Rehman; Qian Li; Syed Mumtaz Hussain; Rahat Ali; Syed Asim Hussain (Lithos, 2025)

Green-engineered calcium-doped carbon nanospheres enhance salt tolerance and growth in maize by modulating gene expressions and antioxidant defense mechanisms - Muhammad Haseeb Javaid; Bahar Ali; Asifa Neelam; Syed Asad Hussain Bukhari; Raheel Munir; Zulqarnain Haider; Muhammad Rehman; Hafiza Arooj Razzaq; Abdul Majeed; Yinbo Gan (Journal of Environmental Chemical Engineering, 2025)

Tailoring g-C3N4 properties through P and K co-doping: advancing photocatalytic CO2 reduction to CH4 - Ahmed Ismail; Muhammad Zahid; Bilal Ahmad; Salman Hayat; Sher Ali; Syed ul Hasnain Bakhtiar; Abdullah N. Alodhayb; Xiaoqiang Wu; Qaisar Alam; Sharafat Ali; Liang Qiao (Chemical Engineering Journal, 2025)

Combined Impact of Waste Water and Farm Yard Manure on Growth of Tomato (Solanum lycopersicum L.) and Soil Health: A Sustainable Agriculture Approach - Arsalan Saghir; Muhammad Sohail Akram; Shahzad Ali; Shahla Rashid; Muhammad Ajmal Farhad; Hafiz Muhammad Tayyab Khan; Syed Ayyaz javed; Mohammad Raish; Muhammad Khubaib (Journal of Soil Science and Plant Nutrition, 2025)

Effect of Phosphorus Modified Cotton Stick Biochar on Growth, Photosynthesis, Enzymatic Activities and Lead (Pb) Uptake in Tomato Plants Grown in Pb-contaminated Soil - Zaffar Malik; Aleena Shabir; Ahmad Ali; Muhammad Naveed Aslam; Humera Aziz; Syed Farhan Haider Bukhari; Sana Noreen; Usama Ali Tahir; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2025)

N-Dimethyl chalcone facilitated augmentation of IL-10 and diminution of TNF-α, IL-1β, IL-6, NFκB, and COX-2 in FCA-induced arthritic rat model - Faiza Waseem; Ali Sharif; Maryam Shabbir; Bushra Akhtar; Syed Wadood Ali Shah; Shahnaz; Adeel Arshad; Ejaz Basheer; Muhammad Asif Hanif; Muhammad Ali (Inflammopharmacology, 2025)

Relative change in accommodation space and sedimentation rates of Jurassic to Middle Eocene sedimentary facies in the NW Himalaya, Pakistan - Tariq Mahmood; Naveed Ahsan; Muhammad Armaghan Faisal Miraj; Shaukat Ali; Faisal Shah; Syed Kamran Ali (Carbonates and Evaporites, 2025)

The role of corroles in modern cancer therapy: innovation and prospects - Laiba Javaid; Huma Hameed; Mahtab Ahmad Khan; Syed Muhammad Ahmad; Inaba Shujaat Qureshi; Rabia Shahzad; Ali Irfan (BioMetals, 2025)

Molecular characterization and drug resistance pattern in pol gene of HIV-1 sub-subtypes circulating in Lahore, Pakistan - Akmal Zubair; Adnan Zeb; Syed Ahsan Shahid; Hasnain Javed; Muhammad Ali (Virus Genes, 2025)

Effect of Diagenetic Processes and Depositional Facies on Reservoir Quality of the Eocene Carbonate Sequence (Sakesar Limestone) in the Central Salt Range, Pakistan - Naveed Rehman; Shu Jiang; Syed Haroon Ali; Asim Falak Naz; Muhammad Tariq (Journal of Earth Science, 2025)

Dietary zinc requirement of Catla (Catla catla) juveniles - Anam Zafar; Syed Zakir Hussain Shah; Mahroze Fatima; Syed Makhdoom Hussain; Muhammad Mudassar Shahzad; Majid Hussain; Wazir Ali (Aquaculture International, 2025)

Quantitative analysis of pathogenesis-related protein expression in Gossypium hirsutum L. to elicitor-induced resistance against cotton leaf curl disease and predicted in-silico protein-protein interactions - Muhammad Fahad Khan; Syed Atif Hasan Naqvi; Adnan Iqbal; Seth Alan Steichen; Amjad Ali; Rana Muhammad Amir Gulzar; Judith K. Brown; Ummad Ud Din Umar (Physiological and Molecular Plant Pathology, 2025)

Investigating the interaction of breed and seasonality on milk quality parameters in different dairy cow breeds - Hafiz Muhammad Jawad Saleem; Qamar Abbas Syed; Sumayah Abbas; Muhammad Azeem; Saba Anwar; Ali Hassan (Food and Humanity, 2025)

Interactive effects of soil moisture and temperature on chromium-induced microbial and enzymatic stress - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Muhammad Akmal; Muhammad Abid Ali Khan; Muhammad Umer Iqbal; Niaz Ahmad; Mahmoud Moustafa; Mohammed O. Alshaharni; Uthman Algopishi (World Journal of Microbiology and Biotechnology, 2025)

Advanced Permeability Prediction Through Two-Dimensional Geological Feature Image Extraction with CNN Regression from Well Logs Data - Wakeel Hussain; Miao Luo; Muhammad Ali; Syed Naheel Raza Rizvi; Harith F. Al-Khafaji; Nafees Ali; Salah Alshareef Alkfakey Ahmed (Mathematical Geosciences, 2025)

Insights into Wild Medicinal Plants: Assessing Mineral Profiles in the Ojhor Valley, Chitral, Pakistan - Muhammad Nauman Khan; Barkat Ullah; Alevcan Kaplan; Abdul Razzaq; Ghulam Jelani; Sana Wahab; Syed Nasar Shah; Nazima Wahid; Muhammad Adnan; Mohamed Farouk Elsadek; M. Ajmal Ali; Majid Iqbal (Biological Trace Element Research, 2025)

Estimation and geographical mapping of enteric methane emission from large ruminants under different production systems in Pakistan - Nasir Ali; Muhammad Qamar Shahid; Nisar Ahmad; Syed Ghulam Mohayud Din Hashmi (Tropical Animal Health and Production, 2025)

Coral diversity and abundance patterns at the West Coast of Sabah: a case study of Kota Kinabalu coral reefs - Khodzori Fikri Akmal; Nor’ashikin Aslam Zuhairi; Zepri Abdul Muhaimin; Zarinah Waheed; Muhammad Ali Syed Hussein; Gan Sze Hoon; Yee Tong Kiu; Khairul Hisham Hariz; Mazni Muhammad Addin; Siti Nur Hazwani Oslan (Community Ecology, 2025)

Nano-revolution in aquaculture: quantum dot innovations for sustainable fisheries - Ulfat Batool; Syed Makhdoom Hussain; Shafaqat Ali; Azhar Rasul; Muhammad Mudassar Shahzad; Adan Naeem; Nisar Ahmad; Muhammad Munir; Abdul Ghafoor; Mohammad Ali Alshehri (Aquaculture International, 2025)

ICT-driven urbanization and energy security risk: Empirical evidence from Group 7 and Emerging 7 economies - Ahmed Usman; Syed Muhammad Muddassir Abbas Naqvi; Ilhan Ozturk; Ali Hassan; Asma Arif (Environmental Impact Assessment Review, 2025)

Effect of resveratrol on post-thaw motility, kinematics, structural parameters and antioxidant/oxidant status of Kamori buck spermatozoa - Tarique Hussain; Muhammad Hammad Fayyaz; Amjad Hameed; Syed Murtaz Hassan Andrabi; Rehana Kausar; Yasin Mubashir; Iqra Batool; Muhammad Shahzad; Ali Dogan Omur (Cryobiology, 2025)

Fish waste biorefinery: A novel approach to promote industrial sustainability - Javaeria Maqsood Gill; Syed Makhdoom Hussain; Shafaqat Ali; Abdul Ghafoor; Muhammad Adrees; Nadia Nazish; Adan Naeem; Eman Naeem; Mohammed Ali Alshehri; Eram Rashid (Bioresource Technology, 2025)

RETRACTED ARTICLE: Ameliorating Nickel-Induced Stress in Hypophthalmichthys molitrix (Silver Carp) Through Piper nigrum Extract Supplementation - Syed Muhammad Farhan Ali Shah; Syed Makhdoom Hussain; Shafaqat Ali; Pallab K. Sarker; Khalid A. Al-Ghanim; Sunakbaeva Dilara (Biological Trace Element Research, 2025)

Modified approach to estimate effective porosity using density and neutron logging data in conventional and unconventional reservoirs - Muhammad Abid; Jing Ba; Uti Ikitsombika Markus; Zeeshan Tariq; Syed Haroon Ali (Journal of Applied Geophysics, 2025)

Corrigendum to ‘The protective roles of Oryza glumaepatula and phytohormone in enhancing rice tolerance to cadmium stress by regulating gene expression, morphological, physiological, and antioxidant defense system’ [Environ. Pollut. 364P1 (2024) 125311] - Humera Ashraf; Fozia Ghouri; Shafaqat Ali; Syed Asad Hussain Bukhari; Fasih Ullah Haider; Minghui Zhong; Weiwei Xia; Xuelin Fu; Muhammad Qasim Shahid (Environmental Pollution, 2025)

Impacts of microplastic accumulation in aquatic environment: Physiological, eco-toxicological, immunological, and neurotoxic effects - Eram Rashid; Syed Makhdoom Hussain; Shafaqat Ali; Muhammad Munir; Abdul Ghafoor; Ebru Yilmaz; Mohammed Ali Alshehri; Danish Riaz; Adan Naeem; Eman Naeem (Aquatic Toxicology, 2025)

Non-effervescent Polymeric Floating Tablets of Clarithromycin and Pantoprazole: Preparation and In-Vitro Evaluation for Improved Gastric Drug Retention - Fahad Ashraf; Kifayat Ullah Shah; Muhammad Danish Saeed; Faiqa Falak Naz; Fahad Y. Sabei; Tahseen Ahmed; Syed Shafqat Ali Shah; Amir Badshah; Naeem Ur Rehman; Kausar Ali Mahsud (Journal of Pharmaceutical Innovation, 2025)

Systematic implication of trichome morphology in alpine flora from Hindukush Mountain range - Muhammad Abdullah; Zahid Ullah; Syed Muhammad Iqbal Shah; Mushtaq Ahmad; Amjad Khan; Hussain Shah; Ateef Ullah; Shabir Ahmad; Mohammed Fahad Albeshr; Okezie Emmanuel; Hameed Ullah; Rahman Ali Khan (Genetic Resources and Crop Evolution, 2025)

Evaluating the safety and effectiveness of tolvaptan in patients with heart failure and renal impairment: a systematic review and meta-analysis - Aashish Kumar; Umer Iqbal; Shafin Bin Amin; Syed Ali Arsal; Syed Muhammad Sinaan Ali; Muhammad Ashir Shafique; Muhammad Saad Shahid; Aimen Naz; Emediong Santhus Asuka (European Journal of Clinical Pharmacology, 2025)

A novel (−)-(2S)-7,4′-dihydroxyflavanone compound for treating age-related diabetes mellitus through immunoinformatics-guided activation of CISD3 - Abdur-Rehman Munir; Saad Ilyas Baig; Muhammad Asif Razzaq; Fatima Rauf; Yasir Ali; Syed Muhammad Abdullah Azam (Biogerontology, 2025)

Exposure to spaceflight enhances the virulence of Purpureocillium lilacinum against Tetranychus cinnabarinus: modulation of the host’s enzyme activities and microbiome - Xiaoxiao Wang; Fangzhao Yi; Chengli Zou; Qi Yan; Muhammad Hamid Bashir; Waqar Ahmed; Syed Usman Mahmood; Jianhui Wu; Shaukat Ali (Archives of Microbiology, 2025)

Exploring hotspots of traffic accidents in Chiniot-Sargodha Road, Punjab, Pakistan - Taimoor Ashraf; Muhammad Irfan Ahamad; Shakeel Mahmood; Jiangtao Fu; Muhammad Sajid Mehmood; Adnanul Rehman; Sohail Abbas; Syed Ali Asad Naqvi; Rana Muhammad Zulqarnain (Environment, Development and Sustainability, 2025)

Quantifying non-target seahorse fisheries and domestic traditional medicine-based trade in Malaysia - Reana May Yen Ng; Adam Chee Ooi Lim; Chin Nurhiqwanalina Binti Henry Chin Siew Lee; Norazliana Binti Abdul Majib; Muhammad Ali Syed Hussein; Amy Yee-Hui Then (Fisheries Research, 2025)

Developing Ag3VO4@ZnO electrode material for efficient oxygen evolution reaction showcasing its potential for sustainable energy applications - Ali Junaid; Faiqa Noreen; Abdus Sami; Karam Jabbour; Khadija Bibi; Muhammad Ammar Hassan Shah; Nigarish Bano; Muhammad Shuaib Khan; Asma A. Alothman; Syed Imran Abbas Shah (Fuel, 2025)

Probiotic potential and biotechnological characterization of the selected enterococcal strains - Abrar Hussain; Muhammad Shakeel; Muhammad Tanweer Khan; Syed Abid Ali (Food Bioscience, 2025)

The protective roles of Oryza glumaepatula and phytohormone in enhancing rice tolerance to cadmium stress by regulating gene expression, morphological, physiological, and antioxidant defense system - Humera Ashraf; Fozia Ghouri; Shafaqat Ali; Syed Asad Hussain Bukhari; Fasih Ullah Haider; Minghui Zhong; Weiwei Xia; Xuelin Fu; Muhammad Qasim Shahid (Environmental Pollution, 2025)

Spore morphometric analysis in Sino-Himalayan and W-Himalayan Athyriaceae taxa: taxonomic insights and molecular phylogenetic comparison - Syed Nasar Shah; Mushtaq Ahmad; Mohammad Javed Ansari; Muhammad Nauman Khan; Majid Iqbal; Baber Ali; Sami Al Obaid (Genetic Resources and Crop Evolution, 2025)

Advancing plant disease classification: A robust and generalized approach with transformer-fused convolution and Wasserstein domain adaptation - Muhammad Hanif Tunio; Jian ping Li; Xiaoyang Zeng; Awais Ahmed; Syed Attique Shah; Hisam-Uddin Shaikh; Ghulam Ali Mallah; Imam Abdullahi Yahya (Computers and Electronics in Agriculture, 2024)

Rice and heavy metals: A review of cadmium impact and potential remediation techniques - Weiwei Xia; Fozia Ghouri; Minghui Zhong; Syed Asad Hussain Bukhari; Shafaqat Ali; Muhammad Qasim Shahid (Science of The Total Environment, 2024)

Overview of industrial food fraud and authentication through chromatography technique and its impact on public health - Nabila Aslam; Rida Fatima; Ammar B. Altemimi; Talha Ahmad; Samran Khalid; Syed Ali Hassan; Rana Muhammad Aadil (Food Chemistry, 2024)

Fabrication and characterization of bioactive curdlan and sodium alginate films for enhancing the shelf life of Volvariella volvacea - Asif Ali Khan; Feng-Jie Cui; Muhammad Wajid Ullah; Abdul Qayum; Ibrahim Khalifa; Syed Asim Shah Bacha; Zheng-Zi Ying; Ismail Khan; Umar Zeb; Abdullah A. Alarfaj; Mohammad Javed Ansari; Yan Yang; et al. (Food Bioscience, 2024)

Structure-property relationship of ultrasound-assisted nanoemulsion-impregnated bioactive polysaccharide films for enhanced shelf life of mushrooms - Asif Ali Khan; Muhammad Wajid Ullah; Abdul Qayum; Ibrahim Khalifa; Mazhar Ul-Islam; Syed Asim Shah Bacha; Umar Zeb; Fang-Jie Yao; Sulaiman Ali Alharbi; Mansour Shrahili; Yan Yang; Wei Jia; et al. (Food Packaging and Shelf Life, 2024)

Molecular epidemiology of brucellosis in Asia: insights from genotyping analyses - Shahzad Ali; Areeba Mushtaq; Laiba Hassan; Muhammad Ali Syed; Jeffrey T. Foster; Maryam Dadar (Veterinary Research Communications, 2024)

Correction to: Spatio-temporal dynamics of the vector-born plant disease model - Emad Fadhal; Mohamed Mahyoub Al-Shamiri; Muhammad Waqas Yasin; Syed Muhammad Hamza Ashfaq; Nauman Ahmed; Ali Raza; Muhammad Rafiq (Modeling Earth Systems and Environment, 2024)

Spatio-temporal dynamics of the vector-born plant disease model - Emad Fadhal; Mohamed Mahyoub Al-Shamiri; Muhammad Waqas Yasin; Syed Muhammad Hamza Ashfaq; Nauman Ahmed; Ali Raza; Muhammad Rafiq (Modeling Earth Systems and Environment, 2024)

Nitrogen and carbohydrate metabolisms are key factors in maize (Zea mays L.) germination under chromium-induced ROS - Muhammad Imran Atta; Syeda Sadaf Zehra; Zhihang Zhuo; Habib Ali; Malik Waseem Abbas; Syed Naveed Abbas; Sadia Sarwar; Fatima Muneer; Irfan Ahmad; Danpping Xu; Hasham S. Almoallim; Mohammad Javed Ansari (Journal of Plant Diseases and Protection, 2024)

Characterization and Quantification of Outcrops Exposed Along the Karakoram Highway (KKH) and Part of Central Karakoram National Park (CKNP), North Pakistan; Implications for Geoheritage Assessments and Geosite Recognition - Muhammad Yaseen; Jawad Ahmad; Muhammad Naveed Anjum; Abbas Ali Naseem; Syed Tanvir Shah (Geoheritage, 2024)

Deposition and diagenesis of the Triassic-Jurassic limestone successions of the northwestern passive margin of the Indian plate, Sulaiman Fold-Thrust Belt, Pakistan - Razzaq Abdul Manan; Akhtar Muhammad Kassi; Henrik Friis; Aimal Khan Kasi; Syed Haroon Ali; Mohammad Ahmed Farooqui; Muhammad Ishaq Kakar (Carbonates and Evaporites, 2024)

RETRACTED ARTICLE: Therapeutic Potential of Aloe vera and Aloe vera–Conjugated Silver Nanoparticles on Mice Exposed to Hexavalent Chromium - Tooba Nauroze; Shaukat Ali; Shagufta Andleeb; Chaman Ara; Iqra Liaqat; Hina Mushtaq; Samaira Mumtaz; Lubna Kanwal; Afshan Syed Abbas; Shumaila Mumtaz; Muhammad Adeel Farooq; Istaqlal Hussain Khan (Biological Trace Element Research, 2024)

Polygonum bistorta Linn. as a green source for synthesis of biocompatible selenium nanoparticles with potent antimicrobial and antioxidant properties - Hafiz Abdul Haseeb; Muhammad Aslam Khan; Hassam Rasheed; Muhammad Usman Zahid; Thu Dung Doan; Muhammad Aamir Ramzan Siddique; Uzair Ahmad; Syed Ali Imran Bokhari (BioMetals, 2024)

Spatio-temporal analysis of hydrometeorological variables for terrestrial and groundwater storage assessment - Muhammad Shareef Shazil; Sheharyar Ahmad; Syed Amer Mahmood; Syed Ali Asad Naqvi; Sanju Purohit; Aqil Tariq (Groundwater for Sustainable Development, 2024)

Microsatellite Markers & Mitochondrial D-Loop Based Phylogenetic And Diversity Analysis In Gabrali Cattle - Farhad Ali; Syed Muhammad Suhail; Farhan Anwar Khan; Ijaz Ahmad (Tropical Animal Health and Production, 2024)

Does the sustainability committee matter in the efficacy of sustainability reporting and firm performance? - Syed Quaid Ali Shah; Fong Woon Lai; Muhammad Kashif Shad; Salaheldin Hamad; Muhammad Tahir (Environment, Development and Sustainability, 2024)

Deciphering fungicide resistance in Phytophthora: mechanisms, prevalence, and sustainable management approaches - Syed Atif Hasan Naqvi; Muhammad Farhan; Muhammad Ahmad; Rafia Kiran; Noor Fatima; Muhammad Shahbaz; Muhammad Akram; Jaya Seelan Sathiya Seelan; Amjad Ali; Salman Ahmad (World Journal of Microbiology and Biotechnology, 2024)

Flaxseed mucilage—a green additive for the enhancement of water-based mud system characteristics - Faiza Kanwal; Shaine Mohammadali Lalji; Syed Imran Ali; Muneeb Burney; Muhammad Ovais Tariq; Leena Hasan Ahmed; Umer Ahmed Khan; Aashan Sheikh; Muhammad Salman (Arabian Journal of Geosciences, 2024)

Antioxidant dimension and potential as bacterial growth inhibitors in crude extracts of two Artemisia species (Artemisia indica Willd. and Artemisia maritima L.) from Gilgit-Baltistan region, Pakistan - Hassam Rasheed; Adil Hussain; Muhammad Aslam Khan; Mujtaba Hassan; Syed Ali Imran Bokhari (Vegetos, 2024)

First report of Pythium aphanidermatum causing stem and root rot disease on sesame (Sesamum indicum L.) in Punjab, Pakistan - Nasir Ahmed Rajput; Muhammad Atiq; Abdul Mubeen Lodhi; Rehana Naz Syed; Owais Iqbal; Muhammad Usman Ali; Muhammad Wahab; Hadeed Ahmad (Journal of Plant Pathology, 2024)

Fault root cause analysis using degree of change and mean variable threshold limit in non-linear dynamic distillation column - Muhammad Shahid; Haslinda Zabiri; Syed Ali Ammar Taqvi; Mansoor Hai (Process Safety and Environmental Protection, 2024)

Integration of dual band radio waves and ensemble-based approach for rice moisture content determination and localisation - Noraini Azmi; Latifah Munirah Kamarudin; Ahmad Shakaff Ali Yeon; Ammar Zakaria; Syed Muhammad Mamduh Syed Zakaria; Hiromitsu Nishizaki; Latifah Mohamed; Xiaoyang Mao; Mohd Hafiz Fazalul Rahiman (Journal of Stored Products Research, 2024)

The Cambrian sedimentology and reservoir properties of the hybrid Abbottabad Formation in the Kotli area, Sub-Himalaya, Pakistan: insights into the Proto-Tethys paleoenvironment - Syed Kamran Ali; Rafiq Ahmad Lashari; Ali Ghulam Sahito; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Tariq Mahmood (Carbonates and Evaporites, 2024)

First report of Pythium aphanidermatum causing coriander damping-off in district Hyderabad, Sindh, Pakistan - Ghulam Sarwar Shah; Jamal-U-Ddin Hajano; Rehana Naz Syed; Muhammad Ibrahim Khaskheli; Manzoor Ali Abro; Muhammad Ali Khanzada; Abdul Mubeen Lodhi (Journal of Plant Pathology, 2024)

Biochemical and nutritional analysis of seaweed (Iyengaria stellata) and its therapeutic significance, using antioxidant, antimicrobial, and hypoglycemic activities - Muhammad Imran; Arshad Iqbal; Arwa Abdulkreem AL-Huqail; Suliman Mohammed Suliman Alghanem; Syed Lal Badshah; Saad Alghamdi; Mazen Almehmadi; Uthman Balgith Algopishi; Baber Ali; Saima Sohni; Muhammad Ammar Javed; Doaa Bahaa Eldin Darwish (South African Journal of Botany, 2024)

Multinomial classification of NLRP3 inhibitory compounds based on large scale machine learning approaches - Muhammad Ishfaq; Syed Zahid Ali Shah; Ijaz Ahmad; Ziaur Rahman (Molecular Diversity, 2024)

Efficacy of activated carbon using Salvadora persica stem for remediation of potentially toxic dyes from aqueous solution - Muhammad Bilal; Wahid Ullah; Tahir Abbas; Javed Ali; Syed Shah Hassan; Esraa M. Bakhsh; Kalsoom Akhtar; Sher Bahadar Khan (Environmental Monitoring and Assessment, 2024)

Exploring the variability of root system architecture under drought stress in heat-tolerant spring-wheat lines - Asadullah; Shahmir Ali Kalhoro; Wajid Farhad; Azhar Iqbal; Sultan; Abdul Waheed; Muhammad Rashid; Syed Rehmat Ullah Shah (Plant and Soil, 2024)
Background and aims Global wheat production is under threat due to climate change, specifically heat and drought and their combination. This study aims to address the root trait responses of heat-tolerant wheat genotypes to drought. Methods The variability in root traits of CIMMYT wheat lines, which were previously developed for heat stress tolerance (HTWL), was evaluated alongside 10 Pakistani-approved varieties under three cultivation conditions and soil moisture levels. Results Our findings revealed that the plasticity of the wheat root system is highly pronounced, with rhizosphere conditions exerting a more substantial influence (5–49%) than the genotypic response (1–14%). Furthermore, in the hydroponic and pot system, we noted higher maximum-root length (1.5–1.8 fold) and root-to-shoot ratio (3.4–10.6 fold) as compared to field condition, while the root biomass was substantially higher in the field trial (3-57 fold). Nonetheless, persistent drought conditions exerted contrasting impact with reduction in most of the traits except specific root length and harvest index which were increased under drought. Conclusions The variation in root traits against drought indicates the potential for the development of improved genotypes that can withstand multiple stresses. Furthermore, it is crucial to consider rhizosphere conditions when selecting genotypes, as the plasticity of wheat roots may lead to misinterpretations if rhizosphere conditions are disregarded. Root dry weight and root-to-shoot ratio are more stable traits as compared to maximum root length and specific root length. It is recommended to evaluate a broader range of rhizosphere conditions to select tolerant genotypes.

Insight into mechanism of excellent visible-light photocatalytic activity of CuO/MgO/ZnO nanocomposite for advanced solution of environmental remediation - Muhammad Imran; Mohsin Raza; Hadia Noor; Sadia Muniza Faraz; Ali Raza; Umar Farooq; Mohammad Ehtisham Khan; Syed Kashif Ali; Omer Y. Bakather; Wahid Ali; Abdullateef H. Bashiri; Waleed Zakri (Chemosphere, 2024)

Geochemical insights of arsenic mobilization into the aquifers of Punjab, Pakistan - Muhammad Sadiq; Syed Ali Musstjab Akber Shah Eqani; Joel Podgorski; Shazia Ilyas; Syed Sayyam Abbas; Mustafa Nawaz Shafqat; Ismat Nawaz; Michael Berg (Science of The Total Environment, 2024)

Dietary nano-Selenium supplementation improves growth performance, nutrient digestibility and hematology in Cirrhinus mrigala fingerlings - Nisar Ahmad; Syed Makhdoom Hussain; Shafaqat Ali; Pallab K. Sarker; Khalid A. Al-Ghanim; Muhammad Mahmood (Journal of Trace Elements in Medicine and Biology, 2024)

Facilitated transport of ferrihydrite with phosphate under saturated flow conditions - Tufail Shah; Kang Zhao; Ai Chen; Atif Muhmood; Syed Atizaz Ali Shah; Muhammad Kashif Irshad; Yuji Arai; Jianying Shang (Journal of Contaminant Hydrology, 2024)

Characteristics and health implications of fine particulate matter near urban road site in Islamabad, Pakistan - Sabir Hussain; Azhar Siddique; Mujtaba Hassan; Kashif Rasool; Asif Shahzad; Syed Ali Asad Naqvi; Muhammad Raza Ul Mustafa (Environmental Research, 2024)

Assessment of flexural performance of reinforced mud sandwich panels: experimental and numerical modeling approach - Muhammad Waleed Sarwar; Mohammad Adil; Zahid Ullah; Muhammad Ali Sikandar; Muhammad Tariq Bashir; Zafar Baloch; Syed Azmat Ali Shah (Innovative Infrastructure Solutions, 2024)

Techno-economic and performance assessment of a hybrid fuel cell-based combined heat and power system for dairy industry - Kashif Najeeb; Abdul Haseeb Tariq; Muhammad Hassan; Mustafa Anwar; Ali Bahadar; Syed Ali Abbas Kazmi; Muhammad Yousif (Environment, Development and Sustainability, 2024)

Modern ecofriendly approach for extraction of luteolin natural dye from weld for silk fabric and wool yarn dyeing - Syed Ali Raza Naqvi; Kaif ul-Wara; Shahid Adeel; Rony Mia; Mozhgan Hosseinnezhad; Luqman Jameel Rather; Muhammad Imran (Sustainable Chemistry and Pharmacy, 2024)

Characterization of the tubby-like proteins (TLPs) gene family in Cucumis sativus L.: insights into the evolution, structure, and expression patterns under salt stress - Ikram Ullah; Muhammad Uzair; Obaid Ur Rehman; Safira Attacha; Kotb A. Attia; Sheraz Ahmad; Muhammad Salman; Hamid Ali; Muhammad Abdul Rehman Rashid; Asmaa M. Abushady; Sajid Fiaz; Syed Jehangir Shah; et al. (Genetic Resources and Crop Evolution, 2024)

ANN and regression based quantification framework for climate change impact assessment on a weak transmission grid of a developing country across Horizon 2050 plus - M. Mahad Malik; Hamza Waheed Asim; Syed Ali Abbas Kazmi; Kamran Mujahid; Muhammad Waleed Ansari (Environment, Development and Sustainability, 2024)

Association of polymorphism in the promotor area of the caprine BMPR1B gene with litter size and body measurement traits in Damani goats - Inayat Ullah; Rajwali Khan; Syed Muhammad Suhail; Ijaz Ahmad; Farhan Anwar Khan; Muhammad Shoaib; Kamran Farid; Amel Ayari-Akkari; Ekhlas Ali Morfeine (Tropical Animal Health and Production, 2024)

Appraisal of the health hazards associated with the ingestion of vegetables contaminated with potentially toxic elements - Ali Afzal; Atif Muhmood; Syed Ayyaz Javed; Arslan Nazarat; Muhammad Rashid; Asrar Hussain Shah; Farhana Siddique (Arabian Journal of Geosciences, 2024)

An appealing review of industrial and nutraceutical applications of pistachio waste - Syed Ali Hassan; Mueen Abbas; Sania Zia; Abid Aslam Maan; Muhammad Kashif Iqbal Khan; Abdo Hassoun; Aamir Shehzad; Richard Gattin; Rana Muhammad Aadil (Critical Reviews in Food Science and Nutrition, 2024)

Highly selective and effective oxidation of 5-hydroxymethylfurfural by Co-Ni based electrodeposited bimetallic oxide nanostructures - Ghazala Nawaz; Mahnoor Fatima; Zahoor Ahmad; Khurram Saleem Joya; Mohammed Ali Assiri; Syed Imran Abbas Shah; Farhat Yasmeen; Muhammad Naeem Khan (Fuel, 2024)

Differential capacity of phragmites ecotypes in remediation of inorganic contaminants in coastal ecosystems: Implications for climate change - Noreen Akhter; Muhammad Aqeel; Shazia; Muhammad Kashif Irshad; Muhammad Muslim Shehnaz; Sang Soo Lee; Ali Noman; Asad Syed; A. Bokhari; Ali H. Bahkali; Ling Shing Wong (Environmental Research, 2024)

Toxicological assessment of dietary exposure of polyethylene microplastics on growth, nutrient digestibility, carcass and gut histology of Nile Tilapia (Oreochromis niloticus) fingerlings - Muhammad Mahmood; Syed Makhdoom Hussain; Pallab K. Sarker; Shafaqat Ali; Muhammad Saleem Arif; Nadia Nazish; Danish Riaz; Nisar Ahmad; Bilal Ahamad Paray; Adan Naeem (Ecotoxicology, 2024)

Correction to: Domperidone nanocrystals with boosted oral bioavailability: fabrication, evaluation and molecular insight into the polymer-domperidone nanocrystal interaction - Stalielson Tatenda Ndlovu; Naseem Ullah; Shahzeb Khan; Pritika Ramharack; Mahmoud Soliman; Marcel de Matas; Muhammad Shahid; Muhammad Sohail; Muhammad Imran; Syed Wadood Ali Shah; Zahid Hussain (Drug Delivery and Translational Research, 2024)

Predicting asphaltene adsorption on Fe3O4 nanoparticle using machine learning algorithms - Syed Imran Ali; Shaine Mohammadali Lalji; Usama Ahsan; Syed Muhammad Ali; Yassar Kamal Zia; Sajid Hussain; Muneeb Burney; Muhammad Qasim; Zeeshan Ahmad Arfeen (Arabian Journal of Geosciences, 2024)

Unveiling Intricacies of Mango Malformation Dynamics Caused by Fusarium solani Through Extensive Field Surveys and Laboratory, Epidemiology, and Model-Based Insights - Abdurrehman; Talha Mansoor; Muhammad Nasir Subhani; Muhammad Tariq Malik; Ammarah Hasnain; Aqleem Abbas; Abdulwahed Fahad Alrefaei; Haider Ali; Muhammad Zeeshan Hassan; Syed Atif Hasan Naqvi (Applied Fruit Science, 2024)

Linking energy-based circularity with environment in high-income economies - Muhammad Usman; Syed Asif Ali Naqvi; Sofia Anwar; Abdul Majeed Nadeem (Environmental Science and Pollution Research, 2024)

Human biomonitoring of trace metals from different altitudinal settings of Pakistan - Syed Ali Musstjab Akber Shah Eqani; Ambreen Alamdar; Ismat Nawaz; Syed Sayyam Abbas Shah; Tasawar Khanam; Qurat Ul Ain Hayder; Muhammad Sohail; Ioannis A. Katsoyiannis; Heqing Shen (Environmental Science and Pollution Research, 2024)

Molecular prevalence of vector borne bacterial pathogens in the blood samples of wild rodent species trapped from Saudi Arabia - Abdul Ghafar; Samia Q. Alghamdi; Abdullah D. Alanazi; Syed Muhammad Zukhruf Qousain; Maryam Ijaz; Muhammad Naeem; Muhammad Ali; Hira Muqaddas; Adil Khan; Furhan Iqbal (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Seasonal Variation and Association of Heavy Metals in the Vital Organs of Edible Fishes from the River Jhelum in Punjab, Pakistan - Iram Inayat; Aima Iram Batool; Muhammad Fayyaz Ur Rehman; Khawaja Raees Ahmad; Muhammad Ali Kanwal; Rabiyah Ali; Rameen Khalid; Syed Sikandar Habib (Biological Trace Element Research, 2024)

Effect of riboflavin on redox balance, osmolyte accumulation, methylglyoxal generation and nutrient acquisition in indian squash (Praecitrullus fistulosus L.) under chromium toxicity - Habiba Kanwal; Syed Hammad Raza; Shafaqat Ali; Muhammad Iqbal; Mudassir Iqbal Shad (Environmental Science and Pollution Research, 2024)

Marine Streptomyces sp. PGC 39: A treasure trove of new antimicrobial agents, macrolidycin, and pyrachlomycin - Rabbia Ahmad; Muhammad Imran Tousif; Mamona Nazir; Asma Yaqoob; Syed Adnan Ali Shah; Gokhan Zengin; Abdullahi Ibrahim Uba; Shabbir Muhammad (Food Bioscience, 2024)

Barriers affecting implementation of life cycle cost analysis in construction projects: SEM approach - Muhammad Altaf; Wesam Salah Alaloul; Muhammad Ali Musarat; Sherif Mostafa; Rodney Stewart; Ali Hussain; Muhammad Babar Ali Rabbani; Syed Saad; Syed Ammad (Innovative Infrastructure Solutions, 2024)

Cerium oxide nanoparticles improve the post-thaw quality and in-vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Muhammad Shahbaz Yousaf; Nisar Ahmad; Sajid Khan Tahir; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman; Hafsa Zaneb; et al. (Theriogenology, 2024)

CRISPR/Cas9-based genome editing: A revolutionary approach for crop improvement and global food security - Ghulam Muha-Ud-Din; Faizan Ali; Akhtar Hameed; Syed Atif Hasan Naqvi; Mir Muhammad Nizamani; Muhammad Jabran; Sohaib Sarfraz; Wang Yong (Physiological and Molecular Plant Pathology, 2024)

Spherical Fe2O3 nanoparticles inhibit the production of aflatoxins (B1 and B2) and regulate total soluble solids and titratable acidity of peach fruit - Mahnoor Akbar; Naeem Ali; Muhammad Imran; Arshad Hussain; Syed Waqas Hassan; Urooj Haroon; Asif Kamal; Farhana; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (International Journal of Food Microbiology, 2024)

Biochemical profile of Vaucheria karachiensis and evaluation of its nutritional, antioxidant, antimicrobial, and hypoglycemic potentials - Arshad Iqbal; Muhammad Imran; Syed Lal Badshah; Ashwag Shami; Baber Ali; Zamarud Shah; Muhammad Ayaz; Abdulrahman Alasmari; Marzough Aziz Albalawi; Amin A. Al-Doaiss; Majed A. Bajaber; Sezai Ercisli (Algal Research, 2024)

How ESG reporting is effected by sustainable finance and green innovation: moderating role of sales growth - Fawad Rauf; Wang Wanqiu; Khwaja Naveed; Syed Usman Qadri; Muhammad Sibt e Ali (Environmental Science and Pollution Research, 2023)

Turbid reefs experience lower coral bleaching effects in NE Borneo (Sabah, Malaysia) - Allia Rosedy; Isabel Ives; Zarinah Waheed; Muhammad Ali Syed Hussein; Sindia Sosdian; Kenneth Johnson; Nadia Santodomingo (Regional Studies in Marine Science, 2023)

Green synthesis of cobalt ferrite and Mn doped cobalt ferrite nanoparticles: Anticancer, antidiabetic and antibacterial studies - Sabahat Fiaz; Muhammad Naeem Ahmed; Ihsan ul Haq; Syed Wadood Ali Shah; Muhammad Waseem (Journal of Trace Elements in Medicine and Biology, 2023)

Feeding ethogram of Antilochus coquebertii F. preying on Dysdercus koenigii - Adeel Mukhtar; Muhammad Usama Altaf; Muhammad Ikhlaq; Waqar Jaleel; Syed Muhammad Zaka; Asad Ali; Zahid Hanif (Journal of Asia-Pacific Entomology, 2023)

A multi-criteria decision model to support sustainable building energy management system with intelligent automation - Muhammad Uzair; Syed Ali Abbas Kazmi (Energy and Buildings, 2023)

Improved bio-oil yield from thermo-catalytic pyrolysis of Citrus limetta waste over pumice: Determination of kinetic parameters using Kissinger method - Faisal Muhammad; Jan Nisar; Ghulam Ali; Farooq Anwar; Syed Tasleem Hussain; Sher Wali Khan (Bioresource Technology Reports, 2023)

Exploring the hidden treasures of Nitella hyalina: a comprehensive study on its biological compounds, nutritional profile, and unveiling its antimicrobial, antioxidative, and hypoglycemic properties - Muhammad Imran; Arshad Iqbal; Syed Lal Badshah; Imtiaz Ahmad; Ashwag Shami; Baber Ali; Fatema Suliman Alatawi; Mohsen Suliman Alatawi; Yasser S. Mostafa; Saad A. Alamri; Ahlam A. Alalwiat; Majed A. Bajaber (World Journal of Microbiology and Biotechnology, 2023)

Effects of prenatal dichromatic light exposure on hatching results and post-hatch performance of Japanese quail - Muhammad Safwan; Shahid Mehmood; Shahid Sherzada; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi; Shaheryar Ali; Abd ur Rehman; Muhammad Faisal Riaz; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; et al. (Tropical Animal Health and Production, 2023)

Subtractive sequence analysis aided druggable targets mining in Burkholderia cepacia complex and finding inhibitors through bioinformatics approach - Syed Shah Hassan; Rida Shams; Ihosvany Camps; Zarrin Basharat; Saman Sohail; Yasmin Khan; Asad Ullah; Muhammad Irfan; Javed Ali; Muhammad Bilal; Carlos M. Morel (Molecular Diversity, 2023)

Production, purification, and characterization of p-diphenol oxidase (PDO) enzyme from lignolytic fungal isolate Schizophyllum commune MF-O5 - Muhammad Faheem; Syed Ali Imran Bokhari; Muhammad Arshad Malik; Bashir Ahmad; Muhammad Riaz; Nafeesa Zahid; Adil Hussain; Abdul Ghani; Hanif Ullah; Waseem Shah; Rashid Mehmood; Khurshid Ahmad; et al. (Folia Microbiologica, 2023)

A decline in snow cover area of Passu and Ghulkin valleys between 1995 and 2022 - Imran Hussain; Mumtaz Ali; Sher Muhammad; Wajid Hassan; Salar Ali; Zakir Hussain; Syed Hammad Ali; Shaukat Ali; Muhammad Younis Khan (Journal of Mountain Science, 2023)

Unlocking the secrets of soil microbes: How decades-long contamination and heavy metals accumulation from sewage water and industrial effluents shape soil biological health - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Niaz Ahmed; Sajjad Hussain; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Javeed Shabbir Dar; Mahmoud Moustafa; Mohammed O. Alshaharni (Chemosphere, 2023)

Multiple phases of yttrium-doped molybdenum trioxide nanorods as efficient dye degrader and bactericidal agents with molecular docking analysis - Muhammad Ikram; Tahira Shujah; Anum Shahzadi; Ali Haider; Aqsa Rafique; Anwar Ul-Hamid; Walid Nabgan; Syed Karrar Haider; Thamraa Alshahrani; Mohammed M. Algaradah; S. Amber Yousaf; Junaid Haider (Chemosphere, 2023)

A contemplating review on different synthesis methods of 2D-Molybdenum disulfide (MoS2) nanosheets - Syed Shujaat Karim; Abubakar Sudais; Muhammad Salman Shah; Sarah Farrukh; Subhan Ali; Mubashir Ahmed; Zarrar Salahuddin; Xianfeng Fan (Fuel, 2023)

LS8pyCalc: semi-automated Python calculator to retrieve land surface temperature, cross verified through in situ and MODIS datasets - Mamoon Ur Rasheed; Syed Amer Mahmood; Rao Mansor Ali Khan; Muhammad Abdullah Sohl (Arabian Journal of Geosciences, 2023)

Bactericidal role of epidermal mucus of freshwater fish treated with Aeromonas hydrophila - Shandana Ali; Syed Ata Ur Rahman Shah; Muhammad Rauf; Maizom Hassan; Waheed Ullah; Farman Ullah Dawar (Journal of Fish Diseases, 2023)
This study explored the bactericidal role of the epidermal mucus (EM) of five freshwater Cyprinid fish species namely Ctenopharyngodon idella , Labeo rohita , Catla catla , Hypophthalmichthys molitrix , and Cirrhinus mrigala after treatment with Aeromonas hydrophila . Extracts of EM (crude and acidic) of each species showed bactericidal activity against various Gram −ve ( Pseudomonas aeruginosa , Escherichia coli , Aeromonas hydrophila , Edwardsiella tarda , Salmonella enterica , Klebsiella pneumonia , Serratia marcescens , and Enterobacter cloacae ) and Gram +ve ( Bacillus wiedmannii and Staphylococcus aureus ) bacteria compared with standard antibiotics (Fosfomycin). The zone of inhibition (ZOI) was measured in millimetres against antibiotics (Fosfomycin). Variations in bactericidal activity of EM were observed against bacteria from the same and different fish species. The acidic extract was more effective than the crude extract and showed significantly higher ZOI values against various bacteria and Fosfomycin antibiotics. This result shows that fish EM may perform an important role in fish defence against bacteria. Therefore, this study may hint towards the substitution of synthetic antibiotics with fish EM that may be used as a novel ‘bactericidal’ in aquaculture as well as in humans against bacterial infections.

Utilization of cereal-based husks to achieve sustainable development goals: Treatment of wastewater, biofuels, and biodegradable packaging - Syed Ali Hassan; Mueen Abbas; Waqar Mujahid; Waqar Ahmed; Saeed Ahmad; Abid Aslam Maan; Aamir Shehzad; Zuhaib F. Bhat; Rana Muhammad Aadil (Trends in Food Science & Technology, 2023)

Pharmacological and toxicological evaluation of methyl 4-hydroxy-2H-1,2-benzothiazine-3-carboxylate 1,1-dioxoide against haloperidol induced Parkinson like symptoms in animal model: In-vitro and in-vivo studies - Liaqat Hussain; Ina Masood; Matloob Ahmad; Muhammad Yasir Ali; Uzma Saleem; Musaddique Hussain; Syed Haroon Khalid; Zunera Chauhdary (Toxicology and Applied Pharmacology, 2023)

Chronic exposure to electronic waste poses risk to liver toxicity with molecular interaction of GSTM1, GSTT1 null variants, and GSTP1 - Aneela Shoukat; Syed Muhammad Nurulain; Sabir Hussain; Sosan Andleeb Khan; Hussain Ahmed; Zahid Muneer; Syed Tahir Abbas Shah; Saqlain Raza; Syed Ali Musstjab Shah Eqani (Environmental Pollution, 2023)

Enhancement of photocatalytic activity of Ba-doped CoO for degradation of Emamectin benzoate in aqueous solution - Huma Khalid; Atta ul Haq; Syed Ali Raza Naqvi; Muhammad Usman; Tanveer Hussain Bokhari (Environmental Monitoring and Assessment, 2023)

Metamorphism of Ladakh Island Arc terrain in the Himalayan region: implications from sulfide geochemistry and petrography - Muhammad Farhan; Mohammad Arif; Ying Ye; Chun-Feng Li; Xuegang Chen; Tao Wu; Zaheen Ullah; Syed Ali Turab; Tehseen Zafar; Zahid Hussain; Izhar Sadiq; Mubasir Ali (Arabian Journal of Geosciences, 2023)

Diversity of arthropods in citrus orchards of Sargodha, Pakistan: Use of different trapping techniques - Muhammad Irfan Ullah; Muhammad Arshad; Asad Abdullah; Nimra Altaf; Syed Muhammad Ali Zahid; Muhammad Afzal (International Journal of Tropical Insect Science, 2023)

Techno-economic assessment of sunflower husk pellets treated with waste glycerol for the Bio-Hydrogen production– A Simulation-based case study - Bilal Kazmi; Syed Ali Ammar Taqvi; Salman Raza Naqvi; Asif Ali Mirani; Muhammad Shahbaz; Muhammad Naqvi; Dagmar Juchelková; Gaber E. Eldesoky (Fuel, 2023)

Techno-economic sustainability assessment for bio-hydrogen production based on hybrid blend of biomass: A simulation study - Syed Muhammad Mustafa Rizvi; Bilal kazmi; Syed Ali Ammar Taqvi; Mahwish Mobeen Khan; Haslinda Zabiri; Danial Qadir; Ahmed Sayed M. Metwally (Fuel, 2023)

Investigation of control performance on an absorption/stripping system to remove CO2 achieving clean energy systems - Syed Ali Ammar Taqvi; Haslinda Zabiri; Salvinder Kaur Marik Singh; Lemma Dendena Tufa; Muhammad Naqvi (Fuel, 2023)

Boosting the energy storage performance of aqueous NH4+ symmetric supercapacitor based on the nanostructured molybdenum disulfide nanosheets - Muhammad Sufyan Javed; Xiaofeng Zhang; Salamat Ali; Syed Shoaib Ahmad Shah; Awais Ahmad; Iftikhar Hussain; Shahid Hussain; Shaukat Khan; Mohamed Ouladsmane; Sayed M. Tag ElDin; Waqas Ul Arifeen; Weihua Han (Chemical Engineering Journal, 2023)

Estimating Photosynthetically Active Euphotic Layer in Major Lakes of Kumaun Region Using Secchi Depth - Zainab Khan; Sk Ajim Ali; Mohammad Mohsin; Syed Kausar Shamim; Ekaterina Mankovskaya; Farhana Parvin; Nikhat Bano; Ateeque Ahmad; Muhammad Yousuf Jat Baloch (Water, Air, & Soil Pollution, 2023)

Synthesis of Elemental- and Nano-sulfur-enriched Bio-organic Phosphate Composites, and Their Impact on Nutrients Bioavailability and Maize Growth - Ayesha Shakoor; Ghulam Jilani; Tanveer Iqbal; Imran Mahmood; Tajwar Alam; Muhammad Asif Ali; Syed Shahid Hussain Shah; Rizwan Ahmad (Journal of Soil Science and Plant Nutrition, 2023)

Enhancement of combustion effect leading to improved performance and exhaust emissions of an SI engine with ferrous oxide and graphite nanoparticles - Yasir Hussain Siddiqui; Muhammad Shakaib; Adnan Rasheed; Hafiz Muhammad Ali; Syed Mohammad Rizwan Azeem; Athar Husain Siddique; Muhammad Shafiq (Environmental Science and Pollution Research, 2023)

Antioxidant effects of zinc-oxide nanoparticles on post-thaw quality and in vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Habib Rehman; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Nisar Ahmad; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman (Small Ruminant Research, 2023)

Prevalence and risk factors of bluetongue in small and large ruminants maintained on Government farms in North-western Pakistan - Muhammad Ishaq; Syed Asad Ali Shah; Nadar Khan; Syed M. Jamal (Research in Veterinary Science, 2023)

Single Pot Enzymatic Treatment of Sugarcane Bagasse Using Laccase and Cellulase for the Production of Value-Added Products - Usama Hafeez; Muhammad Sohail; Syed Tariq Ali (Sugar Tech, 2023)

Effect of In Ovo Trace Element Supplementation on Immune-Related Cells of the Small Intestine of Post-hatched Broiler Chicken - Fazul Nabi; Muhammad Asif Arain; Sarfaraz Ali Fazlani; Mariyam Khalid; Firdous Bugti; Sikandar Ali; Syed Khurram Fareed; Juan Liu (Biological Trace Element Research, 2023)

Diversity in Elemental Content in Selected Artemisia L. (Asteraceae) Species from Gilgit-Baltistan Region of Pakistan Based on Inductively Coupled Plasma Atomic Emission Spectrophotometry (ICP-AES) - Adil Hussain; Muhammad Sajid; Daniel Potter; Hassam Rasheed; Mujtaba Hassan; Naeem Akhtar; Bashir Ahmad; Syed Ali Imran Bokhari (Biological Trace Element Research, 2023)

Variations in cold flow and physical properties of Northern Pakistan gas condensate oil after interacting with different polymeric drilling mud systems - Shaine Mohammadali Lalji; Syed Imran Ali; Sajid Hussain; Syed Muhammad Ali; Zeeshan Ali Lashari (Arabian Journal of Geosciences, 2023)

Influence of the chronic groundwater fluoride consumption on cholinergic enzymes, ACHE and BCHE gene SNPs and pro-inflammatory cytokines: A study with Pakistani population groups - Sara Bibi; Rabia Habib; Sania Shafiq; Syed Sayyam Abbas; Shaiza Khan; Syed Ali Musstjab Akber Shah Eqani; Eugenie Nepovimova; Mansoor Shaukat Khan; Kamil Kuca; Syed Muhammad Nurulain (Science of The Total Environment, 2023)

The potential of functionalized graphene-based composites for removing heavy metals and organic pollutants - Muhammad Saqlain Iqbal; Awais Ali Aslam; Ramsha Iftikhar; Muhammad Junaid; Syed Muhammad Imran; Muhammad Shahid Nazir; Zulfiqar Ali; Muhammad Zafar; Ayesha Kanwal; Norinsan Kamil Othman; Ujjwal Pal; Ai Ling Pang; et al. (Journal of Water Process Engineering, 2023)

Evidence and Molecular Characterization of Multidrug Resistant Staphylococcus aureus Isolated From Equines in Pakistan - Farwa Anwaar; Muhammad Ijaz; Hamza Rasheed; Syed Faizan Ali Shah; Syed Ali Raza Haider; Muhammad Jawad Sabir (Journal of Equine Veterinary Science, 2023)

Machine learning - a novel approach to predict the porosity curve using geophysical logs data: An example from the Lower Goru sand reservoir in the Southern Indus Basin, Pakistan - Wakeel Hussain; Miao Luo; Muhammad Ali; Syed Mumtaz Hussain; Sajid Ali; Sartaj Hussain; Asim Falak Naz; Saddam Hussain (Journal of Applied Geophysics, 2023)

Effect of wind and solar energy production, and economic development on the environmental quality: Is this the solution to climate change? - Bilal Hussain; Syed Asif Ali Naqvi; Sofia Anwar; Muhammad Usman (Gondwana Research, 2023)

Aspen plus simulation model of municipal solid waste gasification of metropolitan city for syngas production - Muzaffar Mehdi; Syed Ali Ammar Taqvi; Asif Ahmed Shaikh; Saad Khan; Salman Raza Naqvi; Muhammad Shahbaz; Dagmar Juchelková (Fuel, 2023)

Application of UAV photogrammetry and electrical resistivity tomography for characterization of a complex landslide: a case study from northwest Himalayas, Pakistan - Syed Ahatsham Haider; Matloob Hussain; Aamir Ali; Muhammad Faheem Abbasi; Saad Wani (Natural Hazards, 2023)

Evaluation of phytoremediation potential and resistance of Gladiolus grandiflora L. against cadmium stress - Syed Ali Qasim Bukhari; Aamir Nawaz; Muhammad Dawood (Environmental Geochemistry and Health, 2023)

Variations in the Behaviour, Survival, Haematology, and Biochemistry of Ctenopharyngodon idella (Grass Carp) After Exposure to Commercial Grade Atrazine - Syed Ata Ur Rahman Shah; Muhammad Rauf; Shandana Ali; Sana Ullah; Kalim Ullah; Syed Ishtiaq Anjum; Azizullah Azizullah; Farman Ullah Dawar (Bulletin of Environmental Contamination and Toxicology, 2023)

Sedimentology and reservoir characteristics of Jurassic Samanasuk Formation of Salt Range and Hazara areas, Upper Indus Basin, Pakistan - Syed Umair Ali; Syed Kamran Ali; Khawaja Umair Majeed; Muhammad Haris; Muhammad Zaheer; Tariq Mehmood (Arabian Journal of Geosciences, 2023)

Unveiling the genomic potential of a novel thermostable glycoside hydrolases producing Neobacillus sedimentimangrovi UE25 - Uroosa Ejaz; Faizan Saleem; Rozina Rashid; Khwaja Ali Hasan; Muhammad Noman Syed; Muhammad Sohail (Antonie van Leeuwenhoek, 2023)

A step towards achieving SDG 2030 agenda: Analyzing the predictive power of information globalization amidst technological innovation-environmental stewardship nexus in the greenest economies - Muhammad Ramzan; Sami Ullah; Syed Ali Raza; Muhammad Nadeem (Journal of Environmental Management, 2023)

Potential of pectin-chitosan based composite films embedded with quercetin-loaded nanofillers to control meat associated spoilage bacteria - Syed Muhammad Afroz Ali; Taskeen Niaz; Anas Munir; Ramla Shahid; Saima Shabbir; Tayyaba Noor; Muhammad Imran (Food Bioscience, 2023)

Engineering of oxygen vacancy defect in CeO2 through Mn doping for toluene catalytic oxidation at low temperature - Ahmed Ismail; Muhammad Zahid; Sharafat Ali; Syed ul Hasnain Bakhtiar; Nauman Ali; Adnan Khan; Yujun Zhu (Environmental Research, 2023)

Numerical investigation of thermal-hydraulic design of a printed circuit steam generator - Muhammad Ali Khan; Syed Anas Sohail; Khalid Waheed; Waseem Siddique; Muhammad Ilyas; Fatih Aydogan; Kamran Rasheed Qureshi; Imran Shaban Bhatti (Annals of Nuclear Energy, 2023)

Metallic nanoparticles photodegraded antibiotics and co-application improved wheat growth and nutritional quality through stress alleviation - Anum Amin; Maria Manzoor; Muhammad Wajahat Ramay; Ali Hassan; Kiran Hina; Asad Syed; Ali H. Bahkali; Muhammad Arshad (Chemosphere, 2023)

Green metal oxides coated biochar nanocomposites preparation and its utilization in vertical flow constructed wetlands for reactive dye removal: Performance and kinetics studies - Ruba Munir; Khuram Ali; Syed Abbas Zilqurnain Naqvi; Amna Muneer; Muhammad Zeeshan Bashir; Muhammad Aamer Maqsood; Saima Noreen (Journal of Contaminant Hydrology, 2023)

Impact of technology on the relation between disaggregated energy consumption and CO2 emission in populous countries of Asia - Tang Zhengxia; Zakia Batool; Sajjad Ali; Mohammad Haseeb; Vipin Jain; Syed Muhammad Faraz Raza; Prasun Chakrabarti (Environmental Science and Pollution Research, 2023)

Transition to greener electricity and resource use impact on environmental quality: Policy based study from OECD countries - Muhammad Adnan Bashir; Zhao Dengfeng; Fouzia Amin; Grzegorz Mentel; Syed Ali Raza; Muhammad Farhan Bashir (Utilities Policy, 2023)

Semi-supervised adaptive PLS soft-sensor with PCA-based drift correction method for online valuation of NOx emission in industrial water-tube boiler - Saidatul Hasniza Hasnen; Muhammad Shahid; H. Zabiri; Syed Ali Ammar Taqvi (Process Safety and Environmental Protection, 2023)

Growth responses of mixotrophic giant clams on nearshore turbid coral reefs - Kimberley Mills; Eleanor H. John; Duncan D. Muir; Nadiezhda Santodomingo; Kenneth G. Johnson; Muhammad Ali Syed Hussein; Sindia Sosdian (Coral Reefs, 2023)
Increasing evidence suggests that nearshore turbid coral reefs may mitigate bleaching of reef building calcifiers and play a critical role in the future of marine biodiversity in coastal areas. However, biomineralization processes on turbid reefs are relatively understudied compared to clear water counterparts and most published work focuses on corals. Here, we investigate how the mixotrophic giant clam Tridacna squamosa , a bivalve with ecological, cultural and economic significance, grows across a mosaic of less turbid to turbid reefs in the Coral Triangle. We construct growth chronologies from live and dead collected shells by measuring daily growth increments with petrography and scanning electron microscopy (SEM) to gain insight into growth rate on daily, seasonal and annual scales. We find annual growth is not significantly different across a turbidity gradient when scaled to ontogeny, while seasonal growth highly varies. K d (490) (a measurement positively correlated with turbidity) and chlorophyll- a are likely important factors driving seasonal growth on a turbid reef near a river, compared to sea surface temperature (SST), cloud cover and rainfall on a less turbid reef. On a daily scale, we investigate increment microstructure and spectral characteristics of chronologies, finding a relationship between tidal range and daily increments. Overall, our results indicate that light-enhanced calcification is likely most important in the less turbid reef, compared to heterotrophic feeding in the turbid reef. The trophic plasticity of T. squamosa may allow for its sustained growth in marginal conditions, supporting evidence that these habitats serve as important conservation hotspots for diverse reef building taxa.

Effect of Selenium Nanoparticles and Chitosan on Production Performance and Antioxidant Integrity of Heat-Stressed Broiler - Ghulam Murtaza Lochi; Muhammad Ghiasuddin Shah; Jameel Ahmed Gandahi; Javaid Ali Gadahi; Syed Abdul Hadi; Tanzeela Farooq; Waseem Ali Vistro; Mohammad Malyar Rahmani (Biological Trace Element Research, 2023)

Combined effects of zinc oxide nanoparticles and melatonin on wheat growth, chlorophyll contents, cadmium (Cd) and zinc uptake under Cd stress - Fu Chen; Yuhang Li; Muhammad Zia-ur-Rehman; Syed Makhdoom Hussain; Muhammad Farooq Qayyum; Muhammad Rizwan; Hesham F. Alharby; Nadiyah M. Alabdallah; Basmah M. Alharbi; Shafaqat Ali (Science of The Total Environment, 2023)

Preliminary Geoheritage Assessment of The Gharam Chashma Granitic Batholith (GCGB), Southern Margin of Asian Plate, NW Pakistan: Multiple Constraints from Field Evidence, Petrology, and Physicomechanical Properties - Abbas Ali Naseem; Muhammad Naveed Anjum; Muhammad Yaseen; Muhammad Ali; Waqar Inam; Syed Haroon Ali; Jawad Ahmad; Anees Ahmad Bangash (Geoheritage, 2023)

Sedimentological and Petrographical Characterization of the Cambrian Abbottabad Formation in Kamsar Section, Muzaffarabad Area: Implications for Proto-Tethys Ocean Evolution - Syed Kamran Ali; Rafiq Ahmad Lashari; Ali Ghulam Sahito; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Ahmer Bilal; Tariq Mehmood; Khawaja Umair Majeed (Journal of Marine Science and Engineering, 2023)
The current sedimentological and petrographical research of the Abbottabad Formation has been carried out in order to understand the formation and evolution of the Proto-Tethys Ocean during the Cambrian on the northern margin of the Indian Plate. The Muzaffarabad region is located east of the Upper Indus Basin and the southern part of the Hazara Kashmir Syntaxis. The geological history of the region varies from the Precambrian to the recent period. The Cambrian Abbottabad Formation is well exposed along the Hazara Kashmir Syntaxis at the core of the 500-m-thick Muzaffarabad anticline. The Abbottabad Formation is an unconformity-bounded allo-stratigraphic unit. It has an unconformable lower contact with the Late Precambrian Dogra Formation and an unconformable upper contact with the Paleocene Hangu Formation. The Abbottabad Formation has been divided into four lithofacies, from bottom to top, namely, thinly interbedded dolomite and shale, cherty-stromatolitic dolomite, oxidized limonitic-brecciated zone, and quartzite, with significant lithological changes. Petrographic studies revealed four types of dolomites: fine crystalline dolomite (Dol. I), dolomitic cryptocrystalline chert (Dol. II), algal mat-stromatolitic dolomite (Dol. III), and intraclastic-dolo-grain stone (Dol. IV). The mineral composition of dolostone was analyzed using X-ray diffraction (XRD) and found to be consistent with previous petrographic studies. The dolomite mineral content decreased from base to top, while chert increased towards the top. Elemental weight percentages through energy dispersive X-ray (EDX) analysis show different elements constitute the minerals found in the dolostone, as confirmed by petrographic and XRD analysis. Using outcrop data, facies information, and geochemical data, a modified depositional model of the Abbottabad Formation was developed. During the Early Cambrian period, the formation was deposited in a shallow subtidal to supratidal setting of the Proto-Tethys Ocean. The top of this deposit marks the Cambrian–Paleocene boundary. Because of the progressively coarsening outcrop sequences, this formation seems to be at the very top of the Proto-Tethys Ocean’s shallow marine system.

Photocatalytic degradation of industrial dye using hybrid filler impregnated poly-sulfone membrane and optimizing the catalytic performance using Box-Behnken design - Sadaf Ul Hassan; Sidra Shafique; Bushra Anees Palvasha; Muhammad Haris Saeed; Syed Ali Raza Naqvi; Sohail Nadeem; Syed Irfan; Toheed Akhter; Asim Laeeq Khan; Muhammad Shahid Nazir; Murid Hussain; Young-Kwon Park (Chemosphere, 2023)

Comparison of pixel, sub-pixel and object-based image analysis techniques for co-seismic landslides detection in seismically active area in Lesser Himalaya, Pakistan - Sumbal Bahar Saba; Muhammad Ali; Syed Ali Turab; Muhammad Waseem; Shah Faisal (Natural Hazards, 2023)

Factorial analysis for the impact on filtration properties of water-based drilling fluid after the addition of graphene oxide, pure-bore, and sodium alginate - Shaine Mohammadali Lalji; Syed Imran Ali; Muhammad Mohsin Yousufi; Muhammad Arsalan Sultan; Khizra Fatima; Abdur Rahman Misbah (Arabian Journal of Geosciences, 2023)

Profiling of phthalates, brominated, and organophosphate flame retardants in COVID-19 lockdown house dust; implication on the human health - Nadeem Ali; Muhammad Imtiaz Rashid; Nabil A. Alhakamy; Sultan Hassan Alamri; Syed Ali Musstjab Akber Shah Eqani (Science of The Total Environment, 2023)

Applications of machine learning in thermochemical conversion of biomass-A review - Muzammil khan; Salman Raza Naqvi; Zahid Ullah; Syed Ali Ammar Taqvi; Muhammad Nouman Aslam Khan; Wasif Farooq; Muhammad Taqi Mehran; Dagmar Juchelková; Libor Štěpanec (Fuel, 2023)

Evaluation of single-phase net metering to meet renewable energy targets: A case study from Pakistan - Muhammad Usman Tahir; Kiran Siraj; Syed Faizan Ali Shah; Naveed Arshad (Energy Policy, 2023)

Two-way strategy for enhanced pectinase production: Random mutagenesis and utilization of a halophytic biomass - Asma Hanif; Uroosa Ejaz; Khwaja Ali Hasan; Malaika Karim; Fehmida Suleman; Muskan Siddiq; Syed Faraz Moin; Zainul Abideen; Muhammad Sohail (Biocatalysis and Agricultural Biotechnology, 2023)

Occurrence and Distribution of Heavy Metals in Mining Degraded Soil and Medicinal Plants: A Case Study of Pb/Zn Sulfide Terrain Northern Areas, Pakistan - Javed Nawab; Muhammad Idress; Sajid Ullah; Gul Rukh; Rimsha Zainab; Hassan Sher; Junaid Ghani; Sardar Khan; Zahid Ullah; Imran Ahmad; Syed Weqas Ali (Bulletin of Environmental Contamination and Toxicology, 2023)

A walk of corporate sustainability towards sustainable development: a bibliometric analysis of literature from 2005 to 2021 - Ahmad Ali Jan; Fong-Woon Lai; Junaid Siddique; Muhammad Zahid; Syed Emad Azhar Ali (Environmental Science and Pollution Research, 2022)

Evaluating the safety and efficacy of daprodustat for anemia of chronic kidney disease: a meta-analysis of randomized clinical trials - Kaneez Fatima; Warda Ahmed; Asad Saulat Fatimi; Omar Mahmud; Muhammad Umar Mahar; Ayesha Ali; Syed Roohan Aamir; Muhammad Taha Nasim; Muhammad Bilal Islam; Muhammad Talha Maniya; Dua Azim; Shayan Marsia; et al. (European Journal of Clinical Pharmacology, 2022)

Correction to: Mechanical performance and environmental impact of normal strength concrete incorporating various levels of coconut fiber and recycled aggregates - Syed Haroon Ali Shah; Muhammad Talha Amir; Babar Ali; Mohamed Hechmi El Ouni (Environmental Science and Pollution Research, 2022)

Mechanical performance and environmental impact of normal strength concrete incorporating various levels of coconut fiber and recycled aggregates - Syed Haroon Ali Shah; Muhammad Talha Amir; Babar Ali; Mohamed Hechmi El Ouni (Environmental Science and Pollution Research, 2022)

Capturing spatial variability of factors affecting the water allocation plans—a geo-informatics approach for large irrigation schemes - Muhammad Mohsin Waqas; Muhammad Waseem; Sikandar Ali; Jan W. Hopman; Usman Khalid Awan; Syed Hamid Hussain Shah; Adnan Noor Shah (Environmental Science and Pollution Research, 2022)

Biomonitoring of mercury in water, sediments, and fish (brown and rainbow trout) from remote alpine lakes located in the Himalayas, Pakistan - Javed Nawab; Junaid Ghani; Syed Aziz Ur Rehman; Muhammad Idress; Muhammad Luqman; Sardar Khan; Ali Asghar; Ziaur Rahman (Environmental Science and Pollution Research, 2022)

Effectiveness of various polysaccharides for controlling properties of alkali-activated manganese-rich slag pastes - Shehzad Mussawar; Muhammad Ali Sikandar; Zafar Baloch; Amjad Naseer; Syed Azmat Ali Shah (European Journal of Environmental and Civil Engineering, 2022)

Correction to: Role of casting and curing conditions on the strength and drying shrinkage of greener concrete - Muhammad Nasir; Adeyemi Adesina; Mohammed Ibrahim; Muhammad Umar Khan; Omar S. Baghabra Al‑Amoudi; Syed Imran Ali; Mohammed Maslehuddin; Khalid Saqer Alotaibi (Environmental Science and Pollution Research, 2022)

Role of casting and curing conditions on the strength and drying shrinkage of greener concrete - Muhammad Nasir; Adeyemi Adesina; Mohammed Ibrahim; Muhammad Umar Khan; Omar S. Baghabra Al-Amoudi; Syed Imran Ali; Mohammed Maslehuddin; Khalid Saqer Alotaibi (Environmental Science and Pollution Research, 2022)

Freely dissolved organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) along the Indus River Pakistan: spatial pattern and risk assessment - Muhammad Sohail; Syed Ali Musstjab Akber Shah Eqani; Habib Bokhari; Muhammad Zaffar Hashmi; Nadeem Ali; Ambreen Alamdar; Joel E. Podgorski; Dave Adelman; Rainer Lohmann (Environmental Science and Pollution Research, 2022)

Performance analysis of kinetic models in predicting asphaltene precipitation rate under different conditions of temperature and percentage of precipitant molecular weight - Syed Imran Ali; Shaine Mohammadali Lalji; Zahoor Awan; Saud Hashmi; Muhammad Noman; Nimra Yousaf (Arabian Journal of Geosciences, 2022)

Reverse vaccinology approach for multi-epitope centered vaccine design against delta variant of the SARS-CoV-2 - Khurshid Jalal; Kanwal Khan; Zarrin Basharat; Muhammad Naseer Abbas; Reaz Uddin; Fawad Ali; Saeed Ahmad Khan; Syed Shams ul Hassan (Environmental Science and Pollution Research, 2022)

Determinants of CO2 emissions: exploring the unexplored in low-income countries - Syed Azmat Ali Shah; Syed Quaid Ali Shah; Muhammad Tahir (Environmental Science and Pollution Research, 2022)

Bionomics and management of aphid, Brevicoryne brassicae (Homoptera: Aphididae) on canola (Brassica napus) using Chrysoperla carnea - Muhammad Mamoon-ur-Rashid; Syed Wajhi-ul-Abbas; Habib Ali; Hussan Ara Beghum; Waqar Islam; Madiha Zaynab; Mubasher Hussain; Obaid Ullah Sayal; Habib ur Rehman; Asif Latif (International Journal of Tropical Insect Science, 2022)

Prospect of Anterior Gradient 2 homodimer inhibition via repurposing FDA-approved drugs using structure-based virtual screening - Shafi Ullah; Shafi Ullah Khan; Abbas Khan; Muhammad Junaid; Humaira Rafiq; Thet Thet Htar; Yaxue Zhao; Syed Adnan Ali Shah; Abdul Wadood (Molecular Diversity, 2022)

Cluster bean (Cyamopsis tetragonoloba L.)- a new host of Pythium aphanidermatum - Ghulam Sarwar Shah; Nasir Ahmed Rajput; Rehana Naz Syed; Muhammad Ali Khanzada; Anam Mehwish Khanzada; Owais Iqbal; Abdul Mubeen Lodhi (Journal of Plant Pathology, 2022)

Wheat rust disease detection techniques: a technical perspective - Uferah Shafi; Rafia Mumtaz; Zunaira Shafaq; Syed Mohammad Hassan Zaidi; Muhammad Owais Kaifi; Zahid Mahmood; Syed Ali Raza Zaidi (Journal of Plant Diseases and Protection, 2022)

Recent trends in microalgal harvesting: an overview - Natasha Laraib; Ali Hussain; Arshad Javid; Tahir Noor; Qurat-ul-Ain Ahmad; Asma Chaudhary; Maleeha Manzoor; Muhammad Akmal; Syed Mohsin Bukhari; Waqas Ali; Tae Jin Choi; Peer M. Schenk (Environment, Development and Sustainability, 2022)

Relational pre-impact assessment of conventional housing features and carbon footprint for achieving sustainable built environment - Syed Shujaa Safdar Gardezi; Nasir Shafiq; Muhammad Waris Ali Khan (Environment, Development and Sustainability, 2022)

ICT, renewable energy, financial development, and CO2 emissions in developing countries of East and South Asia - Zakia Batool; Syed Muhammad Faraz Raza; Sajjad Ali; Syed Zain Ul Abidin (Environmental Science and Pollution Research, 2022)

Associations of air pollution concentrations and energy production dynamics in Pakistan during lockdown - Sawaid Abbas; Ghaffar Ali; Faisal Mueen Qamer; Syed Muhammad Irteza (Environmental Science and Pollution Research, 2022)

Evaluation of combined utilization of marble dust powder and fly ash on the properties and sustainability of high-strength concrete - Zaryab Ahmed Rid; Syed Naveed Raza Shah; Muhammad Jaffar Memon; Ashfaque Ahmed Jhatial; Manthar Ali Keerio; Wan Inn Goh (Environmental Science and Pollution Research, 2022)

A review on sources of heavy metals, their toxicity and removal technique using physico-chemical processes from wastewater - Muhammad Rafique; Syeda Hajra; Muhammad Bilal Tahir; Syed Sajid Ali Gillani; Muneeb Irshad (Environmental Science and Pollution Research, 2022)

Moderating role of institutional quality in validation of pollution haven hypothesis in BRICS: a new evidence by using DCCE approach - Imran Sharif Chaudhry; Weihua Yin; Syed Ahtsham Ali; Muhammad Faheem; Qaiser Abbas; Fatima Farooq; Saeed Ur Rahman (Environmental Science and Pollution Research, 2022)

Isolation and molecular characterization of Adenovirus in suspected acute flaccid paralysis patients: A preliminary report from Pakistan - Zainab Khattak; Aamer Ali Shah; Syed Sohail Zahoor Zaidi; Nayab Mahmood; Muhammad Masroor Alam; Salmaan Sharif; Ribqa Akhtar; Yasir Arshid; Muhammad Suleman Rana (Archives of Virology, 2022)

Tocopherol as plant protector: an overview of Tocopherol biosynthesis enzymes and their role as antioxidant and signaling molecules - Essa Ali; Sayed Hussain; Nazim Hussain; Kaleem Ullah Kakar; Jawad Munawar Shah; Syed Hassan Raza Zaidi; Masood Jan; Kewei Zhang; Muhammad Ali Khan; Muhammad Imtiaz (Acta Physiologiae Plantarum, 2022)

Authentication of Halal and Kosher meat and meat products: Analytical approaches, current progresses and future prospects - M. A. Motalib Hossain; Syed Muhammad Kamal Uddin; Sharmin Sultana; Yasmin Abdul Wahab; Suresh Sagadevan; Mohd Rafie Johan; Md. Eaqub Ali (Critical Reviews in Food Science and Nutrition, 2022)

A novel protein truncating mutation in L2HGDH causes L-2-hydroxyglutaric aciduria in a consanguineous Pakistani family - Muhammad Muzammal; Muhammad Zeeshan Ali; Beatrice Brugger; Jasmin Blatterer; Safeer Ahmad; Sundas Taj; Syed Khizar Shah; Saadullah Khan; Christian Enzinger; Erwin Petek; Klaus Wagner; Muzammil Ahmad Khan; et al. (Metabolic Brain Disease, 2022)
Background L-2-hydroxyglutaric aciduria (L2HGA) is a rare neurometabolic disorder that occurs due to accumulation of L-2-hydroxyglutaric acid in the cerebrospinal fluid (CSF), plasma and urine. The clinical manifestation of L2HGA includes intellectual disability, cerebellar ataxia, epilepsy, speech problems and macrocephaly. Methods In the present study, we ascertained a multigenerational consanguineous Pakistani family with 5 affected individuals. Clinical studies were performed through biochemical tests and brain CT scan. Locus mapping was carried out through genome-wide SNP genotyping, whole exome sequencing and Sanger sequencing. For in silico studies protein structural modeling and docking was done using I-TASSER, Cluspro and AutoDock VINA tools. Results Affected individuals presented with cognitive impairment, gait disturbance, speech difficulties and psychomotor delay. Radiologic analysis of a male patient revealed leukoaraiosis with hypoattenuation of cerebral white matter, suggestive of hypomyelination. Homozygosity mapping in this family revealed a linkage region on chromosome 14 between markers rs2039791 and rs781354. Subsequent whole exome analysis identified a novel frameshift mutation NM_024884.3:c.180delG, p.(Ala62Profs*24) in the second exon of L2HGDH . Sanger sequencing confirmed segregation of this mutation with the disease phenotype. The identification of the most N-terminal loss of function mutation published thus far further expands the mutational spectrum of L2HGDH.

Synthesis and evaluation of Ca-doped ferrihydrite as a novel adsorbent for the efficient removal of fluoride - Khalil Ahmad; Izaz Ali Shah; Sharafat Ali; Muhammad Tariq Khan; Muhammad Bilal Ahmed Qureshi; Syed Hassan Ali Shah; Asmat Ali; Wajid Rashid; Hifza Nayab Gul (Environmental Science and Pollution Research, 2022)

Phenomena, factors of wax deposition and its management strategies - Syed Imran Ali; Shaine Mohammadali Lalji; Javed Haneef; Muhammad Arqam Khan; Mohsin Yousufi; Nimra Yousaf; Abdus Saboor (Arabian Journal of Geosciences, 2022)

Depositional Sedimentary Facies, Stratigraphic Control, Paleoecological Constraints, and Paleogeographic Reconstruction of Late Permian Chhidru Formation (Western Salt Range, Pakistan) - Syed Kamran Ali; Hammad Tariq Janjuhah; Syed Muzyan Shahzad; George Kontakiotis; Muhammad Hussain Saleem; Usman Khan; Stergios D. Zarkogiannis; Panayota Makri; Assimina Antonarakou (Journal of Marine Science and Engineering, 2021)
The Upper Indus Basin, in Pakistan’s western Salt Range, is home to the Zaluch Gorge. The sedimentary rocks found in this Gorge, belonging to the Chhidru Formation, were studied in terms of sedimentology and stratigraphy, and provide new insights into the basin paleogeographic evolution from the Precambrian to the Jurassic period. Facies analysis in the Chhidru Formation deposits allowed the recognition of three lithofacies (the limestone facies—CF1, the limestone with clay interbeds facies—CF2, and the sandy limestone facies—CF3) with five microfacies types (mudstone biomicrite—MF-1, wackestone-biomicrite—MF-2, wackestone-biosparite—MF-3, pack-stone-biomicrite—MF-4, and packstone-biosparite—MF-5), as well as their depositional characteristics. The identified carbonate and siliciclastic formations display various facies in a shallow marine environment, with different lithologies, sedimentary features, and energy conditions. It is thought that the depositional characteristics of these microfacies are closer to those of the middle to outer shelf. Because of the progressively coarsening outcrop sequence, this formation seems to be at the very top of the high stand system tract (HST). A modified dynamic depositional model of the Chhidru Formation is further built using outcrop data, facies information, and stratigraphy. According to this concept, the formation was deposited in the middle to inner shelf area of the shallow marine environment, during the Late-Permian period. The Permo-Triassic Boundary (PTB), which is the end of the type-1 series, is marked by this formation’s top.

Aging and its treatment with vitamin C: a comprehensive mechanistic review - Shumaila Mumtaz; Shaukat Ali; Hafiz Muhammad Tahir; Syed Akif Raza Kazmi; Hafiz Abdullah Shakir; Tafail Akbar Mughal; Samaira Mumtaz; Muhammad Summer; Muhammad Adeel Farooq (Molecular Biology Reports, 2021)

Genome-wide identification and characterization of a plant-specific Dof transcription factor gene family in olive (Olea europaea) and its comparison with Arabidopsis - Mariyam; Muhammad Shafiq; Muhammad Haseeb; Rana Muhammad Atif; Syed Agha Armaghan Asad Abbas Naqvi; Numan Ali; Muhammad Arshad Javed; Fizza Gillani; Muhammad Saleem Haider (Horticulture, Environment, and Biotechnology, 2021)

Comparative analysis of chicken cecal microbial diversity and taxonomic composition in response to dietary variation using 16S rRNA amplicon sequencing - Zubia Rashid; Muhammad Zubair Yousaf; Syed Muddassar Hussain Gilani; Sitwat Zehra; Ashaq Ali; Abid Azhar; Saddia Galani (Molecular Biology Reports, 2021)

Mitochondrial phylogenetic and diversity analysis in Azi-Kheli buffalo - Farhad Ali; Ijaz Ahmad; Muhammad Ijaz Ali; Muhammad Hasnain Riaz; Nadar Khan; Obaid Ullah; Faizul Hassan; Syed Muhammad Suhail; Rajwali Khan; Muhammad Tahir Khan; Irshad Ahmad; Muhammad Tariq Zeb (Tropical Animal Health and Production, 2021)

Sources, chemistry, bioremediation and social aspects of arsenic-contaminated waters: a review - Syed Ejaz Hussain Mehdi; Rabia Amen; Awais Ali; Hirra Anjum; Abid Mahmood; Muhammad Mubashir; Ahmad Mukhtar; Sami Ullah; Abdullah G. Al-Sehemi; Muhammad Ibrahim; Mohd Shariq Khan; Muhammad Abdul Qyyum; et al. (Environmental Chemistry Letters, 2021)

In Silico Mutagenesis-Based Remodelling of SARS-CoV-1 Peptide (ATLQAIAS) to Inhibit SARS-CoV-2: Structural-Dynamics and Free Energy Calculations - Abbas Khan; Shaheena Umbreen; Asma Hameed; Rida Fatima; Ujala Zahoor; Zainib Babar; Muhammad Waseem; Zahid Hussain; Muhammad Rizwan; Nasib Zaman; Shahid Ali; Muhammad Suleman; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Processed animal manure improves morpho-physiological and biochemical characteristics of Brassica napus L. under nickel and salinity stress - Muhammad Naveed; Allah Ditta; Maryum Ahmad; Adnan Mustafa; Zulfiqar Ahmad; Manuel Conde-Cid; Shermeen Tahir; Syed Atizaz Ali Shah; Muhammad Mohsin Abrar; Shah Fahad (Environmental Science and Pollution Research, 2021)

Inhibition of jack bean urease by amphiphilic peptides - Zafar Ali Shah; Sadam Hussain; Serab Khan; Nawab Ali; Samiullah Burki; Syed Uzair Ali Shah; Ashfaq Ahmad; Faiz -Ur-Rehman; Muhammad Nasimullah Qureshi; Syed Muhammad Mukrram Shah; Farzana Shaheen (Medicinal Chemistry Research, 2021)

Livelihood diversification in managing catastrophic risks: evidence from flood-disaster regions of Khyber Pakhtunkhwa Province of Pakistan - Ashfaq Ahmad Shah; Zaiwu Gong; Nasir Abbas Khan; Imran Khan; Muhammad Ali; Syed Asif Ali Naqvi (Environmental Science and Pollution Research, 2021)

Regional disparities in Preventive measures of COVID-19 pandemic in China. A study from international students’ prior knowledge, perception and vulnerabilities - Ijaz Younis; Cheng Longsheng; Muhammad Imran Zulfiqar; Muhammad Imran; Syed Ahsan Ali Shah; Mudassar Hussain; Yasir Ahmed Solangi (Environmental Science and Pollution Research, 2021)

COVID-19 transmission, vulnerability, persistence and nanotherapy: a review - Afzal Husain Khan; Vineet Tirth; Manal Fawzy; Alaa El Din Mahmoud; Nadeem A. Khan; Sirajuddin Ahmed; Syed Sadat Ali; Muhammad Akram; Leena Hameed; Saiful Islam; Gotam Das; Sharmili Roy; et al. (Environmental Chemistry Letters, 2021)

Geological and petrographic investigations of the Miocene Molasse deposits in Sub-Himalayas, District Sudhnati, Pakistan - Asim Javed; Ali Wahid; Muhammad Saleem Mughal; Muhammad Sabir Khan; Raja Saad Qammar; Syed Haroon Ali; Numair Ahmad Siddiqui; Muhammad Atif Iqbal (Arabian Journal of Geosciences, 2021)

Long-term fertilization alters chemical composition and stability of aggregate-associated organic carbon in a Chinese red soil: evidence from aggregate fractionation, C mineralization, and 13C NMR analyses - Adnan Mustafa; Xu Hu; Syed Atizaz Ali Shah; Muhammad Mohsin Abrar; Ali Akbar Maitlo; Kashif Ali Kubar; Qudsia Saeed; Muhammad Kamran; Muhammad Naveed; Wang Boren; Sun Nan; Xu Minggang (Journal of Soils and Sediments, 2021)

The impacts of land use/land cover changes on the supply-demand budget of urban ecosystem services - Syed Atif Bokhari; Zafeer Saqib; Amjad Ali; Arif Mahmud; Nadia Akhtar; Ambrina Kanwal; Muhammad Zaman ul Haq (Arabian Journal of Geosciences, 2021)

Impact of stock market, renewable energy consumption and urbanization on environmental degradation: new evidence from BRICS countries - Ijaz Younis; Aziza Naz; Syed Ahsan Ali Shah; Muhammad Nadeem; Cheng Longsheng (Environmental Science and Pollution Research, 2021)

Financial development, international trade, and environmental degradation: a nonlinear threshold model based on panel smooth transition regression - Asadullah Khaskheli; Yushi Jiang; Syed Ali Raza; Komal Akram Khan; Muhammad Asif Qureshi (Environmental Science and Pollution Research, 2021)

Alkaline lipase production by novel meso-tolerant psychrophilic Exiguobacterium sp. strain (AMBL-20) isolated from glacier of northeastern Pakistan - Muhammad Talha Yasin; Yasir Ali; Khurshid Ahmad; Abdul Ghani; Kinza Amanat; Muhammad Mudassir Basheir; Muhammad Faheem; Saddam Hussain; Bashir Ahmad; Adil Hussain; Syed Ali Imran Bokhari (Archives of Microbiology, 2021)

Dietary supplementations of methionine improve growth performances, innate immunity, digestive enzymes, and antioxidant activities of rohu (Labeo rohita) - Zohaib Noor; Mannal Noor; Syed Allauddin Khan; Waqar Younas; Daniya Ualiyeva; Zaigham Hassan; Ali Muhammad Yousafzai (Fish Physiology and Biochemistry, 2021)

Phytosynthesis of poly (ethylene glycol) methacrylate-hybridized gold nanoparticles from C. tuberculata: their structural characterization and potential for in vitro growth in banana - Natasha Anwar; Jan Wahid; Jalal Uddin; Abbas Khan; Mohib Shah; Syed Adil Shah; Fazle Subhan; Mubarak Ali Khan; Kazim Ali; Mamoona Rauf; Muhammad Arif (In Vitro Cellular & Developmental Biology - Plant, 2021)

BBD-Based Development of Itraconazole Loaded Nanostructured Lipid Carrier for Topical Delivery: In Vitro Evaluation and Antimicrobial Assessment - Ameeduzzafar; Mohd Qumber; Nabil K Alruwaili; Syed Nasir Abbas Bukhari; Khalid Saad Alharbi; Syed Sarim Imam; Muhammad Afzal; Bader Alsuwayt; Ali Mujtaba; Asgar Ali (Journal of Pharmaceutical Innovation, 2021)

Arsenic and lead in the indoor residential settings of different socio-economic status; assessment of human health risk via dust exposure - Nadeem Ali; Syed Ali Musstjab Akber Shah Eqani; Ehtisham Nazar; Nabil A. Alhakamy; Muhammad Imtiaz Rashid; Khurram Shahzad; Jahan Zeb; Heqing Shen; Iqbal Mohammad Ibrahim Ismail; Hussain Mohammed Salem Ali Albar (Environmental Science and Pollution Research, 2021)

Threshold non-linear relationship between globalization, renewable energy consumption, and environmental degradation: evidence from smooth transition models - Yushi Jiang; Asadullah Khaskheli; Syed Ali Raza; Muhammad Asif Qureshi; Maiyra Ahmed (Environmental Science and Pollution Research, 2021)

Carbon, nitrogen, and phosphorus stoichiometry mediate sensitivity of carbon stabilization mechanisms along with surface layers of a Mollisol after long-term fertilization in Northeast China - Muhammad Mohsin Abrar; Hu Xu; Tariq Aziz; Nan Sun; Adnan Mustafa; Muhammad Wajahat Aslam; Syed Atizaz Ali Shah; Khalid Mehmood; Baoku Zhou; Xingzhu Ma; Xianni Chen; Minggang Xu (Journal of Soils and Sediments, 2021)

Nephroprotective effect of ethanol extract and fractions of a sea lettuce, Ulva fasciata against cisplatin-induced kidney injury in rats - Nida Sohail; Khan Hira; Junaid Ahmed Kori; Hafiza Farhat; Faizah Urooj; Waqas Khan; Viqar Sultana; Muhammad Shaiq Ali; Syed Ehteshamul-Haque (Environmental Science and Pollution Research, 2021)

Correction to: Effect of Endoxylanase and Iron Oxide Nanoparticles on Performance and Histopathological Features in Broilers - Hamza Rehman; Muzamal Akram; Mubin Mustafa Kiyani; Muhammad Talha Yasin; Abdul Ghani; Javed Iqbal Saggu; Syed Sajid Hussain Shah; Zafar Mahmood Khalid; Syed Ali Imran Bokhari (Biological Trace Element Research, 2021)

Role of fruit volatiles of different guava varieties in attraction and oviposition behaviors of peach fruit fly, Bactrocera zonata Saunders - Muhammad Binyameen; Abdul Hamid; Imran Afzal; Muhammad Sajjad; Muhammad Azeem; Syed Muhammad Zaka; Zahid Mehmood Sarwar; Sarfraz Ali Shad; Thomas C. Baker; Fredrik Schlyter (Arthropod-Plant Interactions, 2021)

Non-linear relationship between tourism, economic growth, urbanization, and environmental degradation: evidence from smooth transition models - Syed Ali Raza; Muhammad Asif Qureshi; Maiyra Ahmed; Shahzad Qaiser; Ramsha Ali; Farhan Ahmed (Environmental Science and Pollution Research, 2021)

Artemisia chamaemelifolia Vill: a rare species of genus Artemisia (Asteraceae-Anthemideae) now present in the northeast (Gilgit-Baltistan) region of Pakistan - Adil Hussain; Muhammad Qasim Hayat; Syed Ali Imran Bokhari (Biologia, 2021)

Synthetic β-hydroxy ketone derivative inhibits cholinesterases, rescues oxidative stress and ameliorates cognitive deficits in 5XFAD mice model of AD - Syed Ilyas Ahmad; Gowhar Ali; Tahir Muhammad; Rahim Ullah; Muhammad Naveed Umar; Aisha Nasir Hashmi (Molecular Biology Reports, 2020)

Measuring education sector resilience in the face of flood disasters in Pakistan: an index-based approach - Ashfaq Ahmad Shah; Zaiwu Gong; Muhammad Ali; Ali Jamshed; Syed Asif Ali Naqvi; Shaista Naz (Environmental Science and Pollution Research, 2020)

Revealing empirical association among ecological footprints, renewable energy consumption, real income, and financial development: a global perspective - Syed Asif Ali Naqvi; Syed Ale Raza Shah; Muhammad Abuzar Mehdi (Environmental Science and Pollution Research, 2020)

Determinants of farmers’ adaptation to climate change in rain-fed agriculture of Pakistan - Sarah Amir; Zafeer Saqib; Muhammad Irfan Khan; Akhter Ali; Muhammad Azeem Khan; Syed Atif Bokhari; Zaman-ul-Haq (Arabian Journal of Geosciences, 2020)

Radon concentration in drinking water and soil after the September 24, 2019, Mw 5.8 earthquake, Mirpur, Azad Jammu, and Kashmir: an evaluation for potential risk - Said Muhammad; Rizwan Ullah; Syed Ali Turab; Muhammad Younis Khan; Nimat Ullah Khattak; Muhammad Asif Khan (Environmental Science and Pollution Research, 2020)

Non-linear threshold effect of financial development on renewable energy consumption: evidence from panel smooth transition regression approach - Syed Ali Raza; Nida Shah; Muhammad Asif Qureshi; Shahzad Qaiser; Ramsha Ali; Farhan Ahmed (Environmental Science and Pollution Research, 2020)

Efficient synthesis of 2,3-diarylbenzo[b]thiophene molecules through palladium (0) Suzuki–Miyaura cross-coupling reaction and their antithrombolyitc, biofilm inhibition, hemolytic potential and molecular docking studies - Nosheen Sial; Nasir Rasool; Komal Rizwan; Ataf Ali Altaf; Shaukat Ali; Ayesha Malik; Muhammad Zubair; Arusa Akhtar; Samia Kausar; Syed Adnan Ali Shah (Medicinal Chemistry Research, 2020)

Environmental degradation, economic growth, and energy innovation: evidence from European countries - Muhammad Ali; Syed Ali Raza; Bilal Khamis (Environmental Science and Pollution Research, 2020)

Intracranial hemorrhage complicating anticoagulant prophylactic therapy in three hospitalized COVID-19 patients - Muhammad Usman Ghani; Mukesh Kumar; Usman Ghani; Fnu Sonia; Syed Ali Abbas (Journal of NeuroVirology, 2020)

Determination of oil contents from eight varieties of olea europaea (Olive) grown in Pakistan - Abdul Khaliq; Syed Muhammad Ali Shah; Muhammad Akram; Naveed Munir; Muhammad Daniyal; Muhammad Irshad; Saeed Ahmad (Natural Product Research, 2020)

Spatial modeling of Dengue prevalence and kriging prediction of Dengue outbreak in Khyber Pakhtunkhwa (Pakistan) using presence only data - Hammad Ahmad; Asad Ali; Syeda Hira Fatima; Farrah Zaidi; Muhammad Khisroon; Syed Basit Rasheed; Ihsan Ullah; Saleem Ullah; Muhammad Shakir (Stochastic Environmental Research and Risk Assessment, 2020)

Toxicity evaluation of pesticide chlorpyrifos in male Japanese quails (Coturnix japonica) - Suliman; Ajmal Khan; Syed Sajjad Ali Shah; Naila Gulfam; Muhammad Khisroon; Muhammad Zahoor (Environmental Science and Pollution Research, 2020)

An Integrated Systems Biology and Network-Based Approaches to Identify Novel Biomarkers in Breast Cancer Cell Lines Using Gene Expression Data - Abbas Khan; Zainab Rehman; Huma Farooque Hashmi; Abdul Aziz Khan; Muhammad Junaid; Abrar Mohammad Sayaf; Syed Shujait Ali; Fakhr Ul Hassan; Wang Heng; Dong-Qing Wei (Interdisciplinary Sciences: Computational Life Sciences, 2020)

Ammonia inhalation-induced inflammation and structural impairment in the bursa of fabricius and thymus of broilers through NF-κB signaling pathway - Syed Waqas Ali Shah; Muhammad Ishfaq; Muhammad Nasrullah; Abdul Qayum; Muhammad Usman Akhtar; Hyeonsoo Jo; Muhammad Hussain; Xiaohua Teng (Environmental Science and Pollution Research, 2020)

Concomitant Treatment of Tannery and Paper Mill Effluents Using Extremely Metal-Tolerant Sulphate-Reducing Bacteria - Muhammad Muneeb; Muhammad Rashid; Arshad Javid; Syed Mohsin Bukhari; Waqas Ali; Ali Hasan; Muhammad Akmal; Ali Hussain (Environmental Processes, 2020)

Lipids as biomarkers of brain disorders - Ghulam Hussain; Haseeb Anwar; Azhar Rasul; Ali Imran; Muhammad Qasim; Shamaila Zafar; Muhammad Imran; Syed Kashif Shahid Kamran; Nimra Aziz; Aroona Razzaq; Waseem Ahmad; Asghar Shabbir; et al. (Critical Reviews in Food Science and Nutrition, 2020)

5-Endo-dig cyclizations in organic syntheses - Muhammad Aamir Sajid; Zulfiqar Ali Khan; Sohail Anjum Shahzad; Syed Ali Raza Naqvi; Muhammad Usman (Molecular Diversity, 2020)

Inhibition of Hyperuricemia and Gouty Arthritis in BALB/c Mice Using Copper Oxide Nanoparticles - Mubin Mustafa Kiyani; Hamza Rehman; Mir Arif Hussain; Saira Jahan; Muhammad Afzal; Irum Nawaz; Tariq Mahmood; Syed Ali Imran Bokhari (Biological Trace Element Research, 2020)

Genotyping of methicillin-resistant Staphylococcus aureus from sepsis patients in Pakistan and detection of antibodies against staphylococcal virulence factors - Stefan Monecke; Muhammad Ali Syed; Mushtaq Ahmad Khan; Shehzad Ahmed; Sadia Tabassum; Darius Gawlik; Elke Müller; Annett Reissig; Sascha D. Braun; Ralf Ehricht (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Genome Wide Identification and Expression Profiles of TALE Genes in Pineapple (Ananas comosus L) - Hina Ali; Yanhui Liu; Syed Muhammad Azam; Imran Ali; Umair Ali; Weimin Li; Hafiza Javaria Ashraf; Yang Jie; Stefan Olsson; Yuan Qin (Tropical Plant Biology, 2019)

Probing the effect of various lipids and polymer blends on clopidogrel encapsulated floating microcarriers - Saba Irshad; Ikram Ullah Khan; Syed Haroon Khalid; Sajid Asghar; Muhammad Irfan; Ikrima Khalid; Nadeem Sabir; Adnan Ali; Ahmad Nawaz Khan; Abid Mehmood Yousaf; Talib Hussain; Yasser Shahzad (DARU Journal of Pharmaceutical Sciences, 2019)

Comparative study of the genetic basis of nitrogen use efficiency in wild and cultivated barley - Jawad Munawar Shah; Sidra tul Muntaha; Essa Ali; Azhar Abbas Khan; Syed Hassan Raza Zaidi; Ahmad Naeem Shahzad; Zeshan Hassan; Ahmad Nawaz; Muhammad Rashid; Syed Asad Hussain Bukhari (Physiology and Molecular Biology of Plants, 2019)

Assessing the solar PV power project site selection in Pakistan: based on AHP-fuzzy VIKOR approach - Yasir Ahmed Solangi; Syed Ahsan Ali Shah; Hashim Zameer; Muhammad Ikram; Burak Omer Saracoglu (Environmental Science and Pollution Research, 2019)

Zinc-lysine prevents chromium-induced morphological, photosynthetic, and oxidative alterations in spinach irrigated with tannery wastewater - Ihsan Elahi Zaheer; Shafaqat Ali; Muhammad Rizwan; Firdaus-e- Bareen; Zohaib Abbas; Syed Asad Hussain Bukhari; Leonard Wijaya; Mohammed Nasser Alyemeni; Parvaiz Ahmad (Environmental Science and Pollution Research, 2019)

Green vehicle adoption behavior among low-income households: evidence from coastal Malaysia - Abdullah Al Mamun; Muhammad Mehedi Masud; Syed Ali Fazal; Rajennd Muniady (Environmental Science and Pollution Research, 2019)

Tamboti wood ash and burnt goat dropping ash, safe alternatives to control cowpea weevils, Callosobruchus maculatus (Fabr.) (Coleoptera: Bruchidae) during storage for subsistence farming - Bamphitlhi Tiroeselea; Gopolang Ranthoakgalea; Muhammad Irfan Ullah; Naunain Mehmood; Syed Muhammad Ali Zahid; Bushra Abid (Environmental Monitoring and Assessment, 2019)

Natural product coumarins: biological and pharmacological perspectives - M. Iftikhar Hussain; Qamar Abbas Syed; Muhammad Nasir Khan Khattak; Baraa Hafez; Manuel J. Reigosa; Ali El-Keblawy (Biologia, 2019)

Estimation of Canal Water Deficit Using Satellite Remote Sensing and GIS: A Case Study in Lower Chenab Canal System - Muhammad Mohsin Waqas; Usman Khalid Awan; Muhammad Jehanzeb Masud Cheema; Ishfaq Ahmad; Matlob Ahmad; Sikandar Ali; Syed Hamid Hussain Shah; Allah Bakhsh; Muhammad Iqbal (Journal of the Indian Society of Remote Sensing, 2019)

Technetium-99m labeled Ibuprofen: Development and biological evaluation using sterile inflammation induced animal models - Naeem-Ul-Haq Khan; Syed Ali Raza Naqvi; Hamza Sohail; Samina Roohi; Muhammad Asghar Jamal (Molecular Biology Reports, 2019)

Oxindole-based chalcones: synthesis and their activity against glycation of proteins - Ayesha Khan; Ajmal Khan; Umar Farooq; Muhammad Taha; Syed Adnan Ali Shah; Sobia Ahsan Halim; Arfa Akram; Mohammed Ziauddin Khan; Abdul Khaliq Jan; Ahmed Al-Harrasi (Medicinal Chemistry Research, 2019)

PEGylation: a promising strategy to overcome challenges to cancer-targeted nanomedicines: a review of challenges to clinical transition and promising resolution - Zahid Hussain; Shahzeb Khan; Muhammad Imran; Muhammad Sohail; Syed Wadood Ali Shah; Marcel de Matas (Drug Delivery and Translational Research, 2019)

Thermodynamic and kinetic insights into plant-mediated detoxification of lead, cadmium, and chromium from aqueous solutions by chemically modified Salvia moorcroftiana leaves - Syed Muhammad Salman; Asad Ali; Behramand Khan; Mehmood Iqbal; Muhammad Alamzeb (Environmental Science and Pollution Research, 2019)

Universal mitochondrial 16s rRNA biomarker for mini-barcode to identify fish species in Malaysian fish products - M. A. Motalib Hossain; Syed Muhammad Kamal Uddin; Zaira Zaman Chowdhury; Sharmin Sultana; Mohd Rafie Johan; Abdul Rohman; Yuny Erwanto; Md. Eaqub Ali (Food Additives & Contaminants: Part A, 2019)

Prevalence and current therapy in chronic liver disorders - Muhammad Daniyal; Muhammad Akram; Rida Zainab; Naveed Munir; Aamir Sharif; Syed Muhammad Ali Shah; Bin Liu; Wei Wang (Inflammopharmacology, 2019)

Forecasting number of ISO 14001 certifications of selected countries: application of even GM (1,1), DGM, and NDGM models - Muhammad Ikram; Amin Mahmoudi; Syed Zulfiqar Ali Shah; Muhammad Mohsin (Environmental Science and Pollution Research, 2019)

Domperidone nanocrystals with boosted oral bioavailability: fabrication, evaluation and molecular insight into the polymer-domperidone nanocrystal interaction - Stalielson Tatenda Ndlovu; Naseem Ullah; Shahzeb Khan; Pritika Ramharack; Mahmoud Soliman; Marcel de Matas; Muhammad Shahid; Muhammad Sohail; Muhammad Imran; Syed Wadood Ali Shah; Zahid Hussain (Drug Delivery and Translational Research, 2019)

Assessment of organochlorine pesticides in the Himalayan riverine ecosystems from Pakistan using passive sampling techniques - Rizwan Ullah; Rehana Asghar; Mujtaba Baqar; Adeel Mahmood; Syeda Nazish Ali; Muhammad Sohail; Ralf B. Schäfer; Syed Ali Musstjab Akber Shah Eqani (Environmental Science and Pollution Research, 2019)

Detection of mineral alteration induced by hydrocarbon microseepages by using remotely sensed data in the Fateh Jang area of the Northern Potwar region of Pakistan - Ayesha Habib; Muhammad Khubaib Abuzar; Ijaz Ahmad; Urooj Shakir; Syed Amer Mahmood; Mumtaz Ali Khan; Muhammad Fahad Mahmood (Arabian Journal of Geosciences, 2019)

A new sulphated flavone and other phytoconstituents from the leaves of Tetracera indica Merr. and their alpha-glucosidase inhibitory activity - Alhassan Muhammad Alhassan; Qamar Uddin Ahmed; Jalifah Latip; Syed Adnan Ali Shah (Natural Product Research, 2019)

5-Aminolevulinic Acid-Induced Heavy Metal Stress Tolerance and Underlying Mechanisms in Plants - Shafaqat Ali; Muhammad Rizwan; Abbu Zaid; Muhammad Saleem Arif; Tahira Yasmeen; Afzal Hussain; Muhammad Rizwan Shahid; Syed Asad Hussain Bukhari; Saddam Hussain; Ghulam Hassan Abbasi (Journal of Plant Growth Regulation, 2018)

Ciprofloxacin: from infection therapy to molecular imaging - Syed Ali Raza Naqvi; Samina Roohi; Anam Iqbal; Tauqir A. Sherazi; Ameer Fawad Zahoor; Muhammad Imran (Molecular Biology Reports, 2018)

Synthesis of Symmetric Bridged Bis-Pyrazolone Based Metal Complex Acid Dyes and their Applications on Leather - Muhammad Ayaz; Muhammad Ayaz; Farman Ali; Aamer Saeed; Asma Khurshid; Ghulam Shabir; Tanveer Ahmad; Syed Asad Raza Kazmi; Hassan Ali Khan (Journal of Fluorescence, 2018)

Identification, Characterization and Expression Profiles of Dof Transcription Factors in Pineapple (Ananas comosus L) - Syed Muhammad Azam; Yanhui Liu; Zia Ur Rahman; Hina Ali; Cheng Yan; Lulu Wang; S. V. G. N. Priyadarshani; Binyan Hu; Xinyu Huang; Junjie Xiong; Yuan Qin (Tropical Plant Biology, 2018)

Hospital-acquired methicillin-resistant Staphylococcus aureus (MRSA) from Pakistan: molecular characterisation by microarray technology - Bushra Jamil; Darius Gawlik; Muhammad Ali Syed; Asim Ali Shah; Shahid Ahmad Abbasi; Elke Müller; Annett Reißig; Ralf Ehricht; Stefan Monecke (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Association of detoxification enzymes with butene-fipronil in larvae and adults of Drosophila melanogaster - Muhammad Shahid Arain; Muhammad Shakeel; Mohammed Esmail Abdalla Elzaki; Muhammad Farooq; Muhammad Hafeez; Muhammad Rafiq Shahid; Syed Ali Haider Shah; Fawad Zafar Ahmad Khan; Qaiser Shakeel; Abdalla Markaz Abdalla Salim; Guo-Qing Li (Environmental Science and Pollution Research, 2018)

Recent trends in ring opening of epoxides with sulfur nucleophiles - Sajjad Ahmad; Ameer Fawad Zahoor; Syed Ali Raza Naqvi; Muhammad Akash (Molecular Diversity, 2018)

Regional climate assessment of precipitation and temperature in Southern Punjab (Pakistan) using SimCLIM climate model for different temporal scales - Asad Amin; Wajid Nasim; Muhammad Mubeen; Saleem Sarwar; Peter Urich; Ashfaq Ahmad; Aftab Wajid; Tasneem Khaliq; Fahd Rasul; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Hussani Mubarak; et al. (Theoretical and Applied Climatology, 2018)

Expression Profiles of Wuschel-Related Homeobox Gene Family in Pineapple (Ananas comosus L) - Zia ur Rahman; Syed Muhammad Azam; Yanhui Liu; Cheng Yan; Hina Ali; Lihua Zhao; Piaojuan Chen; Li Yi; S. V. G. N. Priyadarshani; Qin Yuan (Tropical Plant Biology, 2017)

Potentially Toxic Metals and Biological Contamination in Drinking Water Sources in Chromite Mining-Impacted Areas of Pakistan: A Comparative Study - Javed Nawab; Sardar Khan; Muhammad Amjad Khan; Hassan Sher; Ubaid Ur Rehamn; Sharafat Ali; Syed Mehboob Shah (Exposure and Health, 2017)

Evaluating the health risks of potentially toxic elements through wheat consumption in multi-industrial metropolis of Faisalabad, Pakistan - Qumber Abbas; Balal Yousaf; Guijian Liu; Muhammad Zia-ur-Rehman; Muhammad Ubaid Ali; Mehr Ahmed Mujtaba Munir; Syed Arif Hussain (Environmental Science and Pollution Research, 2017)

A measles outbreak in Sindh, Pakistan caused by a genotype B3 virus - Syed Sohail Zahoor Zaidi; Abdul Hameed; Naeem Ali; Massab Umair; Muhammad Masroor Alam; Muhammad Suleman Rana; Salmaan Sharif; Uzma Bashir Aamir; Shahzad Shaukat; Mehar Angez; Adnan Khurshid; Ribqa Akhtar; et al. (Archives of Virology, 2017)

Currently used organophosphate and brominated flame retardants in the environment of China and other developing countries (2000–2016) - Nadeem Ali; Khurram Shahzad; Muhammad Imtiaz Rashid; Heqing Shen; Iqbal Mohammad Ibrahim Ismail; Syed Ali Musstjab Akber Shah Eqani (Environmental Science and Pollution Research, 2017)

Quality of tube well water intended for irrigation and human consumption with special emphasis on arsenic contamination at the area of Punjab, Pakistan - Atta Rasool; Tangfu Xiao; Abida Farooqi; Muhammad Shafeeque; Yizhang Liu; Muhammad Aqeel Kamran; Ioannis A. Katsoyiannis; Syed Ali Musstjab Akber Shah Eqani (Environmental Geochemistry and Health, 2017)

Citric acid enhanced the antioxidant defense system and chromium uptake by Lemna minor L. grown in hydroponics under Cr stress - Rasham Sallah-Ud-Din; Mujahid Farid; Rashid Saeed; Shafaqat Ali; Muhammad Rizwan; Hafiz Muhammad Tauqeer; Syed Asad Hussain Bukhari (Environmental Science and Pollution Research, 2017)

Phyto-management of Cr-contaminated soils by sunflower hybrids: physiological and biochemical response and metal extractability under Cr stress - Mujahid Farid; Shafaqat Ali; Nudrat Aisha Akram; Muhammad Rizwan; Farhat Abbas; Syed Asad Hussain Bukhari; Rashid Saeed (Environmental Science and Pollution Research, 2017)

Toxicity of butene-fipronil, in comparison with seven other insecticides, in Leptinotarsa decemlineata and Drosophila melanogaster - Muhammad Shahid Arain; Pin-Jun Wan; Muhammad Shakeel; Muhammad Farooq; Xing-Xing Hu; Syed Ali Haider Shah; Muhammad Esmail Abdalla Elzaki; Guo-Qing Li (Phytoparasitica, 2017)

Endophytes from medicinal plants and their potential for producing indole acetic acid, improving seed germination and mitigating oxidative stress - Abdul Latif Khan; Syed Abdullah Gilani; Muhammad Waqas; Khadija Al-Hosni; Salima Al-Khiziri; Yoon-Ha Kim; Liaqat Ali; Sang-Mo Kang; Sajjad Asaf; Raheem Shahzad; Javid Hussain; In-Jung Lee; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

A New Broad-Spectrum Peptide Antibiotic Produced by Bacillus brevis Strain MH9 Isolated from Margalla Hills of Islamabad, Pakistan - Syed Aun Muhammad; Amjad Ali; Anam Naz; Afreenish Hassan; Naeem Riaz; Syed Saeed-ul-Hassan; Saadia Andleeb; Debmalya Barh (International Journal of Peptide Research and Therapeutics, 2016)

Prevalence of Waterborne Diseases in Exposed and Unexposed Clusters Using Biosand Filters in a Rural Community, Sindh, Pakistan - Munir Ahmed Sheikh; Muhammad Ayaz Mustufa; Taj Muhammad Laghari; Binafsha Manzoor; Syed Ali Haider; Safia Bibi; Firdous Imran Ali (Exposure and Health, 2016)

Chaetomium endophytes: a repository of pharmacologically active metabolites - Nighat Fatima; Syed Aun Muhammad; Ibrar Khan; Muneer Ahmed Qazi; Irum Shahzadi; Amara Mumtaz; Muhammad Ali Hashmi; Abida Kalsoom Khan; Tariq Ismail (Acta Physiologiae Plantarum, 2016)

New furocarbazole alkaloids from Lonicera quinquelocularis - Dilfaraz Khan; Shafiullah Khan; Syed Badshah; Hazrat Ali; Hamid Ullah; Zia Muhammad; Simon Woodward (Natural Product Research, 2016)

Development of MY-DRG casemix pharmacy service weights in UKM Medical Centre in Malaysia - Saad Ahmed Ali Jadoo; Syed Mohamed Aljunid; Amrizal Muhammad Nur; Zafar Ahmed; Dexter Van Dort (DARU Journal of Pharmaceutical Sciences, 2015)

Development of sediment load estimation models by using artificial neural networking techniques - Muhammad Hassan; M. Ali Shamim; Ali Sikandar; Imran Mehmood; Imtiaz Ahmed; Syed Zishan Ashiq; Anwar Khitab (Environmental Monitoring and Assessment, 2015)

Neuroprotective effect from stem bark extracts of Knema laurina against H 2 O 2 - and Aβ 1–42 -induced cell death in human SH-SY5Y cells - Norsharina Ismail; Muhammad Nadeem Akhtar; Maznah Ismail; Seema Zareen; Syed Adnan Ali Shah; Nordin Hj Lajis; Saiful N. Tajuddin (Natural Product Research, 2015)

Comparison between regression and ANN models for relationship of soil properties and electrical resistivity - Fahad Irfan Siddiqui; Dur Muhammad Pathan; Syed Baharom Azhar Bin Syed Osman; Munawar Ali Pinjaro; Safiullah Memon (Arabian Journal of Geosciences, 2015)

Effect of plant growth-promoting rhizobacteria inoculation on cadmium (Cd) uptake by Eruca sativa - Muhammad Aqeel Kamran; Jabir Hussain Syed; Syed Ali Musstjab Akber Shah Eqani; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2015)

Predicting streamflows to a multipurpose reservoir using artificial neural networks and regression techniques - Muhammad Hassan; Muhammad Ali Shamim; Hashim Nisar Hashmi; Syed Zishan Ashiq; Imtiaz Ahmed; Ghufran Ahmed Pasha; Usman Ali Naeem; Abdul Razzaq Ghumman; Dawei Han (Earth Science Informatics, 2015)

Evaluating pasture and soil allowance of manganese for Kajli rams grazing in semi-arid environment - Zafar Iqbal Khan; Kafeel Ahmad; Muhammad Ashraf; Syed Ali Hassan Naqvi; Alireza Seidavi; Nudrat Aisha Akram; Vito Laudadio; Vincenzo Tufarelli (Tropical Animal Health and Production, 2015)

Mass burden and estimated flux of heavy metals in Pakistan coast: sedimentary pollution and eco-toxicological concerns - Usman Ali; Riffat Naseem Malik; Jabir Hussain Syed; Ch. Tahir Mehmood; Laura Sánchez-García; Azeem Khalid; Muhammad Jamshed Iqbal Chaudhry (Environmental Science and Pollution Research, 2015)

Random mutagenesis and media optimisation for hyperproduction of cellulase from Bacillus species using proximally analysed Saccharum spontaneum in submerged fermentation - Roheena Abdullah; Wajeeha Zafar; Muhammad Nadeem; Mehwish Iqtedar; Shagufta Naz; Quratulain Syed; Zahid Ali Butt (Natural Product Research, 2015)

Synthesis of indole-2-hydrazones in search of potential leishmanicidal agents - Muhammad Taha; Nor Hadiani Ismail; Muhammad Ali; Khalid M. Khan; Waqas Jamil; Syed Muhammad Kashif; Mohammad Asraf (Medicinal Chemistry Research, 2014)

Photodegradation of Moxifloxacin in Aqueous and Organic Solvents: A Kinetic Study - Iqbal Ahmad; Raheela Bano; Syed Ghulam Musharraf; Sofia Ahmed; Muhammad Ali Sheraz; Qamar ul Arfeen; Muhammad Salman Bhatti; Zufi Shad (AAPS PharmSciTech, 2014)

Effect of emamectin benzoate on life history traits and relative fitness of Spodoptera litura (Lepidoptera: Noctuidae) - Syed Muhammad Zaka; Naeem Abbas; Sarfraz Ali Shad; Rizwan Mustafa Shah (Phytoparasitica, 2014)

Cattle egrets as a biosentinels of persistent organic pollutants exposure - Mudassar Khan; Ashiq Mohammad; Karam Ahad; Athanasios Katsoyiannis; Salman Akbar Malik; Muhammad Abdullaha; Azhar Rashid; Mauro Fasola; Alamdar Hussain; Habib Bokhari; Syed Ali Musstjab Akber Shah Eqani (Environmental Geochemistry and Health, 2014)

Correction for Irrelevant Absorption in Multicomponent Spectrophotometric Assay of Riboflavin, Formylmethylflavin, and Degradation Products: Kinetic Applications - Iqbal Ahmad; Kiran Qadeer; Kefi Iqbal; Sofia Ahmed; Muhammad Ali Sheraz; Syed Abid Ali; Tania Mirza; Ambreen Hafeez (AAPS PharmSciTech, 2013)

The anti-arthritic and anti-oxidative effect of NBD (6-nitro-1,3-benzodioxane) in adjuvant-induced arthritis (AIA) in rats - Syed Uzair Ali Shah; Nadeem Ashraf; Zahid H. Soomro; Muhammad Raza Shah; Nurul Kabir; Shabana Usman Simjee (Inflammation Research, 2012)

Field evolved resistance to carbamates, organophosphates, pyrethroids, and new chemistry insecticides in Spodoptera litura Fab. (Lepidoptera: Noctuidae) - Sarfraz Ali Shad; Ali H. Sayyed; Sahar Fazal; Mushtaq A. Saleem; Syed Muhammad Zaka; Muhammad Ali (Journal of Pest Science, 2012)

TLR4 polymorphisms and disease susceptibility - Mamoona Noreen; Muhammad Ali A. Shah; Sheeba Murad Mall; Shazia Choudhary; Tahir Hussain; Iltaf Ahmed; Syed Fazal Jalil; Muhammad Imran Raza (Inflammation Research, 2012)

Using leaf tip necrosis as a phenotypic marker to predict the presence of durable rust resistance gene pair Lr34/Yr18 in wheat - Syed Jawad Ahmad Shah; Shaukat Hussain; Musharaf Ahmad; Farhatullah; Iftikhar Ali; Muhammad Ibrahim (Journal of General Plant Pathology, 2011)

Novel mutations in the keratin-74 (KRT74) gene underlie autosomal dominant woolly hair/hypotrichosis in Pakistani families - Naveed Wasif; Syed Kamran ul-Hassan Naqvi; Sulman Basit; Nadir Ali; Muhammad Ansar; Wasim Ahmad (Human Genetics, 2011)

Purification and Characterization of Novel α-Amylase from Bacillus subtilis KIBGE HAS - Saeeda Bano; Shah Ali Ul Qader; Afsheen Aman; Muhammad Noman Syed; Abid Azhar (AAPS PharmSciTech, 2011)

Identification of a recurrent insertion mutation in the LDLR gene in a Pakistani family with autosomal dominant hypercholesterolemia - Muhammad Ajmal; Waqas Ahmed; Ahmed Sadeque; Syeda Hafiza Benish Ali; Syed Habib Bokhari; Nuzhat Ahmed; Raheel Qamar (Molecular Biology Reports, 2010)

Peste des petits ruminants virus (PPRV) infection; Its association with species, seasonal variations and geography - Muhammad Abubakar; Syed Muhammad Jamal; Muhammad Javed Arshed; Manzoor Hussain; Qurban Ali (Tropical Animal Health and Production, 2009)

Purification and characterization of xylanases from Thermomyces lanuginosus and its mutant derivative possessing novel kinetic and thermodynamic properties - Syed Ali Imran Bokhari; Farooq Latif; Muhammad Ibrahim Rajoka (World Journal of Microbiology and Biotechnology, 2009)

Novel mutations in G protein-coupled receptor gene (P2RY5) in families with autosomal recessive hypotrichosis (LAH3) - Zahid Azeem; Musharraf Jelani; Gul Naz; Muhammad Tariq; Naveed Wasif; Syed Kamran-ul-Hassan Naqvi; Muhammad Ayub; Masoom Yasinzai; Muhammad Amin-ud-din; Abdul Wali; Ghazanfar Ali; Muhammad Salman Chishti; et al. (Human Genetics, 2008)

A mutation in the lipase H (LIPH) gene underlie autosomal recessive hypotrichosis - Ghazanfar Ali; Muhammad Salman Chishti; Syed Irfan Raza; Peter John; Wasim Ahmad (Human Genetics, 2007)

New insight in staphylococcin research: bacteriocin and/or bacteriocin-like inhibitory substance(s) produced by S. aureus AB188 - Sadia Saeed; Sheikh Ajaz Rasool; Samia Ahmed; Tanweer Khanum; Muhammad Bashir Khan; Atiya Abbasi; Syed Abid Ali (World Journal of Microbiology and Biotechnology, 2006)

Localization of a novel locus for alopecia with mental retardation syndrome to chromosome 3q26.33–q27.3 - Peter John; Ghazanfar Ali; Muhammad S. Chishti; Syed Muhammad S. Naqvi; Suzanne M. Leal; Wasim Ahmad (Human Genetics, 2006)